Aqueous dispersion, aqueous emulsion, coating agent, coated paper, multilayer structure, packaging material and adhesive, and method for producing aqueous emulsion

By using an aqueous dispersion and an aqueous emulsion containing ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers, the problems of reducing the break point strain of the film and insufficient thermal adhesion and water resistance of the aqueous emulsion in the prior art are solved, and the water resistance and tensile elastic modulus of the film are improved, as well as the thermal adhesion and membrane water resistance of the aqueous emulsion are optimized.

CN115298258BActive Publication Date: 2025-02-25KURARAY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180026354.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-30
Filing Date
2021-03-26
Publication Date
2025-02-25
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

In the prior art, the film made of the composition containing PVA and CNF has improved in terms of water resistance, tensile elastic modulus and breakpoint stress, but the breakpoint strain is significantly reduced; while the thermal adhesiveness of the aqueous emulsion and the water resistance of the film are insufficient.

Method used

The aqueous dispersion and aqueous emulsion containing ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers were used. The ethylene unit content of the ethylene-vinyl alcohol copolymer (A) was more than 1 mol % and less than 20 mol %, the viscosity average polymerization degree was between 200 and 5000, and the saponification degree was between 80 and 99.9 mol %, and the content of the cellulose nanofiber was 0.1 to 40 parts by mass relative to 100 parts by mass of the ethylene-vinyl alcohol copolymer (A).

Benefits of technology

A film with improved water resistance, tensile elastic modulus and breakpoint stress and suppressed reduction in breakpoint strain, as well as an aqueous emulsion with excellent heat resistance and water resistance of the film is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 28587
    Figure 28587
  • Figure 236157
    Figure 236157
  • Figure 29457DEST_PATH_IMAGE002
    Figure 29457DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The present invention provides an aqueous dispersion, which can produce a film having improved water resistance, tensile elastic modulus and breaking point stress and suppressed breaking point strain reduction. The present invention relates to an aqueous dispersion, which contains an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers, wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an aqueous dispersion and an aqueous emulsion containing an ethylene-vinyl alcohol copolymer and cellulose nanofibers, a coating agent composed of the aqueous dispersion or the aqueous emulsion, a coated paper and a multilayer structure coated with the coating agent, and an adhesive composed of the aqueous emulsion. Background Art

[0002] Polyvinyl alcohol (hereinafter sometimes referred to as "PVA") is a hydrophilic and crystalline specific synthetic polymer, and is used in a wide range of applications such as adhesives, dispersants, fiber pastes, packaging films, pressure-sensitive adhesives, and coatings.

[0003] As a method for improving various properties required in various applications, the addition of a modifier can be cited. For example, Patent Document 1 describes that hot water resistance and heat resistance are improved by compounding PVA with cellulose nanofibers (hereinafter sometimes referred to as "CNF") having an average fiber diameter of 2 to 150 nm. Patent Document 2 describes that a composition with good operability can be produced with a low viscosity by mixing PVA and CNF using a specific disperser.

[0004] In addition, the aqueous emulsion obtained by emulsion polymerization of vinyl ester monomers using PVA as a dispersant for emulsion polymerization is widely used in various adhesives for paper, woodworking, plastics, etc., various adhesives for impregnated paper and non-woven products, admixtures, casting materials, coatings, paper processing, fiber processing and other fields.

[0005] As the aqueous emulsion, for example, an emulsion obtained by copolymerizing vinyl acetate monomer and N-methylol acrylamide using PVA as a protective colloid has been proposed (see Patent Document 3). In addition, an emulsion (co)polymerization of vinyl acetate or vinyl acetate and (meth) acrylic acid esters has been proposed using modified PVA containing ethylene as a protective colloid (see Patent Document 4).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-242063

[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-156915

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 10-121017

[0011] Patent document 4: Japanese Patent Application Publication No. 11-106727. Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, according to the research of the present inventors, it is clear that the film made using the composition containing PVA and CNF disclosed in Patent Documents 1 and 2 has improved water resistance, tensile elastic modulus and breaking point stress compared to the case without CNF, but the breaking point strain is significantly reduced.

[0014] In addition, the aqueous emulsions disclosed in Patent Documents 3 and 4 have insufficient heat-resistant adhesiveness and water resistance when forming a film.

[0015] Therefore, one of the objects of the present disclosure is to provide an aqueous dispersion capable of producing a film having improved water resistance, tensile elastic modulus, and stress at break, and in which a decrease in strain at break is suppressed.

[0016] Another object of the present disclosure is to provide an aqueous emulsion having excellent heat-resistant adhesiveness and water resistance of the film.

[0017] The present inventors have conducted diligent research and found that the above-mentioned problems can be solved by the present disclosure. The present disclosure relates to the following contents:

[0018] [1] an aqueous dispersion comprising an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers, wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%;

[0019] [2] The aqueous dispersion according to [1], wherein the viscosity average degree of polymerization of the ethylene-vinyl alcohol copolymer (A) is 200 to 5000;

[0020] [3] The aqueous dispersion according to [1] or [2], wherein the saponification degree of the ethylene-vinyl alcohol copolymer (A) is 80 to 99.9 mol%;

[0021] [4] The aqueous dispersion according to any one of [1] to [3], wherein the content of the cellulose nanofibers is 0.1 to 40 parts by mass based on 100 parts by mass of the ethylene-vinyl alcohol copolymer (A);

[0022] [5] The aqueous dispersion according to any one of [1] to [4], wherein the total content of the ethylene-vinyl alcohol copolymer (A) and the cellulose nanofibers in the aqueous dispersion is 0.1 to 30% by mass;

[0023] [6] The aqueous dispersion according to any one of [1] to [5], wherein the block characteristic of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) is 0.90 to 0.99;

[0024] [7] an aqueous emulsion comprising an ethylene-vinyl alcohol copolymer (A) as a dispersant, a polymer (C) containing ethylenically unsaturated monomer units as a dispersoid, and cellulose nanofibers, wherein the content of the cellulose nanofibers is 0.1 to 40 parts by mass based on 100 parts by mass of the ethylene-vinyl alcohol copolymer (A);

[0025] [8] The aqueous emulsion according to [7], wherein the total content of the ethylene-vinyl alcohol copolymer (A) and the cellulose nanofibers is 2 to 35 parts by mass based on 100 parts by mass of the polymer (C);

[0026] [9] The aqueous emulsion according to [7] or [8], wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%;

[0027]

[10] The aqueous emulsion according to any one of [7] to [9], wherein the total content of the ethylene-vinyl alcohol copolymer (A), the polymer (C), and the cellulose nanofibers in the solid content contained in the aqueous emulsion is 55% by mass or more;

[0028]

[11] The aqueous emulsion according to any one of [7] to

[10] , wherein the polymer (C) contains 70% by mass or more of monomer units derived from at least one selected from vinyl ester monomers, (meth)acrylate monomers, styrene monomers and diene monomers, based on all monomer units;

[0029]

[12] A coating agent comprising the aqueous dispersion according to any one of [1] to [6] or the aqueous emulsion according to any one of [7] to

[11] ;

[0030]

[13] The coating agent according to

[12] , which is a paper coating agent;

[0031]

[14] A coated paper comprising paper coated with the paper coating agent according to

[13] ;

[0032]

[15] The coated paper according to

[14] , which is a release paper base paper or oil-resistant paper;

[0033]

[16] A multilayer structure comprising a substrate comprising a resin, wherein the coating agent according to

[12] is applied onto the substrate;

[0034]

[17] The multilayer structure according to

[16] , wherein the resin is at least one resin selected from the group consisting of polyolefin resins, polyester resins and polyamide resins;

[0035]

[18] A packaging material comprising the multilayer structure according to

[16] or

[17] .

[0036]

[19] An adhesive comprising the aqueous dispersion according to any one of [1] to [6] or the aqueous emulsion according to any one of [7] to

[11] ;

[0037]

[20] The method for producing an aqueous emulsion according to any one of [7] to

[11] , comprising: a step (1) of obtaining an aqueous emulsion by emulsion polymerization of an ethylenically unsaturated monomer in the presence of an ethylene-vinyl alcohol copolymer (A); and a step (2) of blending cellulose nanofibers into the aqueous emulsion;

[0038]

[21] A method for producing an aqueous emulsion according to any one of [7] to

[11] , comprising: a step (3) of obtaining an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers; and a step (4) of mixing the aqueous dispersion with an ethylenically unsaturated monomer to carry out emulsion polymerization.

[0039] Effects of the Invention

[0040] According to the present disclosure, it is possible to provide an aqueous dispersion capable of producing a film having improved water resistance, tensile elastic modulus, and stress at break, and in which a decrease in strain at break is suppressed.

[0041] In addition, according to the present disclosure, an aqueous emulsion having excellent heat-resistant adhesiveness and water resistance of the film can be provided.

[0042] Brief description of the attached figure

[0043] Figure 1 This is a schematic diagram of a polymerization apparatus used in Production Examples 1 to 6.

[0044] Figure 2 This is a schematic diagram of an example of a wide blade. DETAILED DESCRIPTION

[0045] Hereinafter, embodiments of the present disclosure will be described. The present disclosure is not limited to the embodiments.

[0046] As a specific embodiment of the present disclosure, there can be mentioned an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers (hereinafter sometimes referred to as "CNF"), wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol % or more and less than 20 mol %.

[0047] In addition, as another embodiment of the present disclosure, an aqueous emulsion can be listed, which includes an ethylene-vinyl alcohol copolymer (A) as a dispersant, a polymer (C) containing ethylenically unsaturated monomer units as a dispersant (hereinafter sometimes referred to as "polymer (C)"), and cellulose nanofibers, wherein the content of the aforementioned cellulose nanofibers is 0.1 to 40 parts by mass relative to 100 parts by mass of the ethylene-vinyl alcohol copolymer (A).

[0048] [Ethylene-vinyl alcohol copolymer (A)]

[0049] The ethylene-vinyl alcohol copolymer (A) is a polymer containing ethylene units and vinyl alcohol units.

[0050] Using the film made by the aqueous dispersion containing the vinyl alcohol polymer and CNF containing no ethylene unit, compared to the situation without CNF, water resistance, tensile elastic modulus and breaking point stress are improved, but the breaking point strain is significantly reduced. On the other hand, the aqueous dispersion of the present disclosure is because it contains ethylene-vinyl alcohol copolymer (A), therefore in the case of being used to make a film, the breaking point strain of the film can be maintained, while excellent water resistance, tensile elastic modulus and breaking point stress can be played. In this way, in order to play the effect of the present disclosure, the content of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) included in the aqueous dispersion of the present disclosure is more than 1 mol % and less than 20 mol %, which is important.

[0051] Since the aqueous emulsion of the present disclosure contains the ethylene-vinyl alcohol copolymer (A), it is excellent in heat-resistant adhesiveness and water resistance of the film.

[0052] The content of ethylene units contained in the ethylene-vinyl alcohol copolymer (A) contained in the aqueous dispersion of the present disclosure is 1 mol % or more and less than 20 mol %.

[0053] The content of the ethylene unit contained in the ethylene-vinyl alcohol copolymer (A) contained in the aqueous emulsion of the present disclosure is not particularly limited.

[0054] In the aqueous dispersion, the content of ethylene units contained in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%. The content of the above-mentioned ethylene units is preferably 1.5 mol% or more, more preferably 2 mol% or more, and is also preferably 2.5 mol% or more, 3 mol% or more, or 3.5 mol% or more. If the content of the above-mentioned ethylene units is above the above-mentioned lower limit, when the aqueous dispersion of the present invention is used to make a film, the strain reduction at the breaking point of the film can be suppressed, and the water resistance, tensile modulus and breaking point stress of the film can be improved. In addition, if the content of the above-mentioned ethylene units is above the above-mentioned lower limit, the coated paper made using the coating agent composed of the aqueous dispersion of the present invention has a tendency to be excellent in water resistance, solvent barrier properties or oil resistance when bending, and the multilayer structure made using the coating agent has a tendency to be excellent in gas barrier properties. In addition, in the aqueous emulsion, the content of the ethylene unit contained in the ethylene-vinyl alcohol copolymer (A) is suitable for more than 1 mol%, more preferably more than 1.5 mol%, further suitable for more than 2 mol%, and also preferably more than 2.5 mol%, more than 3 mol% or more than 3.5 mol%. Furthermore, if the content of the above-mentioned ethylene unit is above the above-mentioned lower limit, the water resistance of the film of the aqueous emulsion of the present invention is more excellent. On the other hand, in the aqueous dispersion, the content of the above-mentioned ethylene unit is suitable for less than 15 mol%, more preferably less than 13 mol%, further suitable for less than 10 mol%, and also preferably less than 8 mol% or less than 5 mol%. In addition, in the aqueous emulsion, the content of the above-mentioned ethylene unit is suitable for less than 20 mol%, more preferably less than 15 mol%, further suitable for less than 13 mol%, particularly suitable for less than 10 mol%, and also preferably less than 8 mol% or less than 5 mol%. In the aqueous dispersion or aqueous emulsion, if the content of the ethylene unit is less than the upper limit, the water solubility of the ethylene-vinyl alcohol copolymer (A) is excellent, and the aqueous dispersion or aqueous emulsion of the present disclosure can be easily produced. In addition, if the amount of ethylene units is less than the upper limit, the dispersibility of CNF becomes good, so that the storage stability of the aqueous dispersion of the present disclosure is excellent, or the coating unevenness of the coating agent composed of the aqueous dispersion of the present disclosure is suppressed.

[0055] The content of ethylene units in the ethylene-vinyl alcohol copolymer (A) can be determined by 1 For example, the content of ethylene units is determined by the precursor or reacetylated product of the ethylene-vinyl alcohol copolymer (A), that is, the vinyl ester copolymer containing ethylene units. 1 More specifically, the vinyl ester copolymer was purified by reprecipitation three or more times with a mixture of n-hexane and acetone, and then dried under reduced pressure at 80°C for three days to obtain a vinyl ester copolymer for analysis. The copolymer was dissolved in DMSO-d6 and 1The measurement is performed using an H-NMR measuring device (e.g., 500 MHz) at 80° C. The content of ethylene units is calculated using the peak of the main chain methine group derived from vinyl ester (4.7 to 5.2 ppm) and the peak of the main chain methylene group derived from ethylene, vinyl ester, and the third component (monomers other than ethylene and vinyl ester) (0.8 to 1.6 ppm).

[0056] The viscosity average polymerization degree of the ethylene-vinyl alcohol copolymer (A) is preferably 200 or more, more preferably 250 or more, further preferably 300 or more, and preferably 400 or more, 500 or more, 600 or more, 700 or more, 900 or more, 1100 or more, or 1300 or more. If the viscosity average polymerization degree is above the lower limit, when a film is made using the aqueous dispersion of the present invention, the strength of the film tends to be excellent. In addition, if the viscosity average polymerization degree is above the lower limit, the mechanical stability of the film of the aqueous emulsion of the present invention is more excellent. The viscosity average polymerization degree is preferably 5000 or less, more preferably 4500 or less, and further preferably 4000 or less, and preferably 3800 or less, 3500 or less, 3000 or less, 2700 or less, 2500 or less, 2300 or less, or 2000 or less. When the viscosity average degree of polymerization is below the upper limit, the viscosity of the aqueous dispersion is appropriately low, and when the aqueous dispersion of the present disclosure is used as a coating agent, for example, it has the advantage of excellent coating properties. In addition, when the viscosity average degree of polymerization is below the upper limit, the handling of the aqueous emulsion becomes easy.

[0057] The viscosity average degree of polymerization of the ethylene-vinyl alcohol copolymer (A) is measured in accordance with JIS K 6726: 1994. Specifically, the intrinsic viscosity [η] (liter / g) of the ethylene-vinyl alcohol copolymer (A) is measured in water at 30° C., and the viscosity average degree of polymerization P is calculated according to the following formula using the value of the intrinsic viscosity [η]. In addition, when the saponification degree of the ethylene-vinyl alcohol copolymer (A) is less than 99.5 mol %, the intrinsic viscosity [η] is measured after saponification is performed until the saponification degree becomes 99.5 mol % or more.

[0058] P = ([η] × 10 4 / 8.29) (1 / 0.62)

[0059] The saponification degree of the ethylene-vinyl alcohol copolymer (A) is preferably 80 mol% or more, more preferably 83 mol% or more, further preferably 85 mol% or more, and preferably 87 mol% or more or 90 mol% or more. If the above-mentioned saponification degree is above the above-mentioned lower limit, the water solubility and emulsion polymerization stability of the ethylene-vinyl alcohol copolymer (A) are more excellent. The saponification degree of the ethylene-vinyl alcohol copolymer (A) is preferably 99.9 mol% or less, more preferably 99.5 mol% or less, further preferably 99 mol% or less, and particularly preferably 98.5 mol% or less. If the above-mentioned saponification degree is below the above-mentioned upper limit, it is easy to stably manufacture the ethylene-vinyl alcohol copolymer (A). The saponification degree of the ethylene-vinyl alcohol copolymer (A) is measured in accordance with JIS K6726:1994.

[0060] The content of 1,2-glycol bond units in the ethylene-vinyl alcohol copolymer (A) is preferably 1.2 mol% or more, more preferably 1.3 mol% or more, and further preferably 1.4 mol% or more. If the content of the above-mentioned 1,2-glycol bond units is above the above-mentioned lower limit, there is a tendency that the productivity of the ethylene-vinyl alcohol copolymer (A) is excellent, and the viscosity stability of the aqueous dispersion and the aqueous emulsion is excellent. The content of 1,2-glycol bond units in the ethylene-vinyl alcohol copolymer (A) is preferably 2.0 mol% or less, more preferably 1.9 mol% or less, and further preferably 1.8 mol% or less. If the content of the above-mentioned 1,2-glycol bond units is below the above-mentioned upper limit, there is a tendency that the productivity of the ethylene-vinyl alcohol copolymer (A) is excellent, and the hue of the ethylene-vinyl alcohol copolymer (A) is excellent.

[0061] The content of 1,2-glycol bond units in the ethylene-vinyl alcohol copolymer (A) can be calculated by 1 The H-NMR measurement was performed. Specifically, the ethylene-vinyl alcohol copolymer (A) was saponified to a saponification degree of 99.9 mol % or more, and then fully washed with methanol and dried under reduced pressure at 90°C for 2 days. A sample prepared by dissolving the obtained completely saponified ethylene-vinyl alcohol copolymer in DMSO-d6 and adding a few drops of trifluoroacetic acid was measured using a 500 MHz NMR. 1 H-NMR was measured at 80° C. The peak of the methine proton derived from the vinyl alcohol unit was at 3.2 to 4.0 ppm (integral value A), and the peak of one methine proton derived from the 1,2-glycol bond was at around 3.15 to 3.35 ppm (integral value B). The content of the 1,2-glycol bond unit can be calculated by the following formula.

[0062] 1,2-diol bond amount (mol%) = B / A × 100

[0063] The block characteristics of the ethylene units of the ethylene-vinyl alcohol copolymer (A) are suitable for being 0.70 or more, more suitable for being 0.80 or more, and further suitable for being 0.90 or more, and there are also cases where it is preferably 0.93 or more or 0.95 or more. If the above-mentioned block characteristics are above the above-mentioned lower limit, there is a tendency that the viscosity stability of the aqueous dispersion of the present invention is excellent, or the high-speed coating property when the aqueous dispersion of the present invention is used as an adhesive is excellent. In addition, if the above-mentioned block characteristics are above the above-mentioned lower limit, the storage stability and heat-resistant adhesion of the aqueous emulsion of the present invention are more excellent at low temperatures. The block characteristics of the ethylene units of the ethylene-vinyl alcohol copolymer (A) are suitable for being 1.1 or less, and there are also cases where it is preferably 1.05 or less, 1.0 or less or 0.99 or less. If the above-mentioned block characteristics are below the above-mentioned upper limit, when a film is made using the aqueous dispersion of the present invention, there is a tendency that the water resistance of the film (skin film) is more excellent. Moreover, when the said block characteristic is below the said upper limit, the heat-resistant adhesiveness of the aqueous emulsion of this disclosure will be more excellent.

[0064] The aqueous dispersion disclosed herein contains ethylene-vinyl alcohol copolymer (A) and CNF, so that when used to make a film, the strain at the breaking point of the film can be maintained, and excellent water resistance, tensile elastic modulus and breaking point stress can be exerted. In addition, the coating agent disclosed herein can provide a coated paper with excellent water resistance, solvent barrier and oil resistance when bending, or a multilayer structure with excellent gas barrier properties, because it contains ethylene-vinyl alcohol copolymer (A) and CNF. The aqueous dispersion disclosed herein has an excellent effect as described above, but regarding dispersibility, in general, an aqueous dispersion containing a vinyl alcohol polymer and CNF containing ethylene units has a poor dispersibility of CNF compared to an aqueous dispersion containing PVA and CNF. It is speculated that this is because when the aqueous dispersion contains PVA, the aggregation or coagulation between CNF is suppressed due to the interaction between PVA and CNF. In contrast, when the aqueous dispersion contains a vinyl alcohol polymer containing ethylene units, due to the presence of ethylene units, the interaction between the vinyl alcohol polymer and CNF is weakened, and it is difficult to suppress the aggregation or coagulation between CNF. On the other hand, in the aqueous dispersion of the present invention, if the block characteristics of the ethylene units of the ethylene-vinyl alcohol copolymer (A) are in a specific range, in addition to being able to exert the effects of the ethylene-vinyl alcohol copolymer (A) and CNF as described above, the dispersibility of the aqueous dispersion can also be well maintained. As a result, the coating agent composed of the aqueous dispersion of the present invention has a tendency to be more excellent in storage stability and coating properties. From this viewpoint, the block characteristics of the ethylene units of the ethylene-vinyl alcohol copolymer (A) are preferably 0.90 or more, more preferably 0.93 or more, and further preferably 0.95 or more, preferably 0.99 or less, more preferably less than 0.99, and further preferably 0.98 or less. The ethylene-vinyl alcohol copolymer (A) having the block characteristics of the ethylene units in the above range can be manufactured using the method described later.

[0065] It should be noted that the aforementioned block characteristics are numerical values ​​indicating the distribution of ethylene units and vinyl alcohol units generated by saponification of vinyl ester units, and take values ​​between 0 and 2. 0 means that ethylene units or vinyl alcohol units are completely distributed in blocks, and as the value increases, the alternation increases, 1 means that ethylene units and vinyl alcohol units are completely randomly present, and 2 means that ethylene units and vinyl alcohol units are completely alternately present. The aforementioned block characteristics can be obtained by 13 C-NMR was determined as follows. First, the ethylene-vinyl alcohol copolymer (A) was saponified to a saponification degree of 99.9 mol % or more, then washed thoroughly with methanol and dried under reduced pressure at 90°C for 2 days. The completely saponified ethylene-vinyl alcohol copolymer was dissolved in DMSO-d6 and analyzed using a 500 MHz 13The obtained sample was measured by C-NMR (Nuclear Magnetic Resonance Device "GX-500" manufactured by JEOL Ltd.) at 80° C. The obtained spectrum was assigned according to the method described in T. Moritani and H. Iwasaki, Vol. 11, No. 6, pp. 1251-1259, Macromolecules (1978), and the block characteristics (η) of the ethylene unit were calculated using the molar fraction (AE) of the two-unit chain of vinyl alcohol and ethylene, the molar fraction (A) of the vinyl alcohol unit, and the molar fraction (E) of the ethylene unit, and the block characteristics (η) of the ethylene unit were calculated by the following formula.

[0066] η=(AE) / {2×(A)×(E)}

[0067] The ethylene-vinyl alcohol copolymer (A) may contain monomer units other than the vinyl alcohol unit, the ethylene unit and the vinyl ester unit as long as the effects of the present disclosure are not impaired. Examples of such monomers include α-olefins such as propylene, n-butene, and isobutylene; acrylic acid and its salts; acrylic acid esters; methacrylic acid and its salts; methacrylic acid esters; acrylamide; acrylamide derivatives such as N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidepropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or its quaternary ammonium salts, and N-hydroxymethylacrylamide and its derivatives; methacrylamide; N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidopropanesulfonic acid and its salts, methacrylamidopropyldimethylamine and its salts or its quaternary ammonium salts, N- Methacrylamide derivatives such as hydroxymethyl methacrylamide and its derivatives; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts or esters; vinyl silyl compounds such as vinyltrimethoxysilane; isopropenyl acetate, etc. The content of these monomers varies depending on the purpose of use, application, etc., but is preferably less than 10 mol%, more preferably less than 5 mol%, further preferably less than 1 mol%, particularly preferably less than 0.5 mol%, and may also be 0 mol%.

[0068] [Method for producing ethylene-vinyl alcohol copolymer (A)]

[0069] The ethylene-vinyl alcohol copolymer (A) is obtained, for example, by copolymerizing ethylene and a vinyl ester monomer to obtain an ethylene-vinyl ester copolymer, saponifying the ethylene-vinyl ester copolymer using a saponification catalyst such as sodium hydroxide, and optionally pulverizing and drying the copolymer.

[0070] As a method for copolymerizing ethylene and vinyl ester monomers, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. Among them, bulk polymerization or solution polymerization in which polymerization is performed without a solvent or in a solvent such as alcohol is generally adopted. As the above-mentioned alcohol, lower alcohols such as methanol, ethanol, and propanol can be cited. As an initiator used for copolymerization, known polymerization initiators such as azo initiators or peroxide initiators such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, and n-propyl peroxydicarbonate can be cited.

[0071] The polymerization temperature is not particularly limited, but is preferably 0°C to 150°C, more preferably room temperature to 150°C, further preferably room temperature to the boiling point of the solvent used, and particularly preferably 30 to 60°C.

[0072] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. Among them, vinyl acetate is preferred.

[0073] When copolymerizing ethylene and vinyl ester monomers, a chain transfer agent may also be used. Examples of chain transfer agents include aldehydes such as acetaldehyde, propionaldehyde, butyraldehyde, and benzaldehyde; ketones such as acetone, methyl ethyl ketone, hexanone, and cyclohexanone; mercaptans such as 2-hydroxyethanethiol; thiocarboxylic acids such as thioacetic acid; halogenated hydrocarbons such as trichloroethylene and perchloroethylene, etc. Among them, aldehydes and ketones are preferred. When a chain transfer agent is used, its amount can be determined based on the chain transfer coefficient of the chain transfer agent used and the degree of polymerization of the target ethylene-vinyl alcohol copolymer (A), and there is no particular limitation, but it is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the vinyl ester monomer.

[0074] The ethylene-vinyl alcohol copolymer (A) is obtained by saponifying the ethylene-vinyl ester copolymer obtained in the polymerization step. At this time, it is preferred to saponify the ethylene-vinyl ester copolymer by alcoholysis or hydrolysis reaction in an organic solvent in the presence of a catalyst. As the catalyst used in the saponification step, alkaline catalysts such as sodium hydroxide, potassium hydroxide, sodium methoxide, etc.; acidic catalysts such as sulfuric acid, hydrochloric acid, p-toluenesulfonic acid, etc. can be listed. The organic solvent used in the saponification step is not particularly limited, and alcohols such as methanol and ethanol can be listed; esters such as methyl acetate and ethyl acetate; ketones such as acetone and methyl ethyl ketone; aromatic hydrocarbons such as benzene and toluene, etc. They can be used alone or in combination of two or more. Among them, it is simple and preferred to use methanol or a mixed solution of methanol and methyl acetate as a solvent and perform a saponification reaction in the presence of sodium hydroxide as an alkaline catalyst. The amount of the saponification catalyst used is preferably 0.001 to 0.5 in terms of the molar ratio relative to the vinyl ester unit in the ethylene-vinyl ester copolymer. The molar ratio is more preferably 0.002 or more. On the other hand, the molar ratio is more preferably 0.4 or less, and further preferably 0.3 or less.

[0075] After the saponification step, a pulverization step and a drying step may be performed. Furthermore, the pulverization step may be divided into a preliminary pulverization step and a main pulverization step. After the saponification step, a washing step for removing impurities such as sodium acetate may be performed as needed.

[0076] In the method for producing the ethylene-vinyl alcohol copolymer (A) disclosed herein, when obtaining the ethylene-vinyl ester copolymer, the following steps are preferably included: (a) in a polymerization tank, using a wide blade, stirring at a power Pv per unit volume of 0.5 to 10 kW / m 3 The solution containing vinyl ester is stirred so that the Froude number Fr becomes 0.05 to 0.2, while being contacted with a gas containing ethylene. By contacting the solution containing vinyl ester with a gas containing ethylene in this way, the block characteristic of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) can be made 0.70 to 0.99, preferably 0.90 to 0.99.

[0077] Below, while referring to the attached Figure 1 A specific polymerization apparatus and a polymerization process using the apparatus will be described. Figure 1 : is a schematic diagram of the polymerization apparatus used in Production Example 1. This apparatus is a continuous tank type reactor, in which a polymerization tank 1 is connected to a heat exchanger 2 via conduits 3 and 4. In the heat exchanger 2, vinyl ester and ethylene can be contacted in countercurrent.

[0078] A plurality of conduits 5, 6, and 7 are connected to the polymerization tank 1. The number and arrangement of the conduits are not limited to the illustrated method. Ethylene, polymerization initiator, and organic solvent are supplied to the polymerization tank 1 through these conduits. For the ratio of the raw materials introduced into the polymerization tank per unit time, it is preferred that ethylene is 0.1 to 20 parts by mass, organic solvent is 1 to 100 parts by mass, and polymerization initiator is 0.00001 to 1 part by mass relative to 100 parts by mass of vinyl ester. Depending on the circumstances, vinyl ester and other monomers may also be supplied through these conduits. The reaction solution in the polymerization tank 1 is continuously discharged from the reaction solution outlet pipe 9 connected to the bottom of the polymerization tank 1.

[0079] A stirrer 8 having a wide blade as a stirring blade is provided in the polymerization tank 1. The solution containing the vinyl ester is brought into contact with an ethylene-containing gas while being stirred using the wide blade, thereby reacting ethylene with the vinyl ester to obtain an ethylene-vinyl ester copolymer.

[0080] As a stirring blade for stirring the solution containing vinyl ester, a broad paddle blade is preferably used. Figure 2 A schematic diagram of an example of a wide blade used in the present disclosure is shown in FIG. Figure 2 As shown, a wide paddle with a width b is a characteristic of the wide paddle wing. The width b of the wide paddle wing can be appropriately adjusted according to the capacity of the polymerization tank 1, etc., but is preferably 1 to 10 m as described later. By using such a paddle, the solution can be uniformly mixed from the bottom to the liquid surface, and at the same time, the solution containing vinyl ester can effectively absorb ethylene. The aforementioned wide paddle wing can be a single stage (for example, a maximum blended wing (Max blended wing)) or a multi-stage (for example, a full zone wing (Fullzone wing)). From the viewpoint of allowing vinyl ester to absorb ethylene more effectively, during the stirring of the solution containing vinyl ester, the liquid level of the solution is preferably located near the upper end of the stirring wing. Specific examples of wide-blade wings include the Maximum Hybrid Wing (Sumitomo Heavy Industries, Ltd.), the Full Cover Wing (Kobelco Environmental Solutions, Ltd.), the Sanmeler Wing (Mitsubishi Heavy Industries, Ltd.), the Hi-Fi Mixer Wing (Soken Chemical Co., Ltd.), the Super-Mix Wing (Sataki Chemical Industries, Ltd., Super-Mix MR203, Super-Mix MR205), and the Bendleaf Wing (Hakko Sangyo Co., Ltd.).

[0081] The ethylene pressure in the polymerization tank during polymerization is preferably 0.01 to 0.9 MPa, more preferably 0.05 to 0.8 MPa, and still more preferably 0.1 to 0.7 MPa. The polymerization rate of vinyl ester at the outlet of the polymerization tank is not particularly limited, but is usually preferably 10 to 90%, and more preferably 15 to 85%.

[0082] The polymerization temperature is not particularly limited, but is usually preferably 0 to 180°C, more preferably 20 to 160°C, and still more preferably 30 to 150°C.

[0083] When ethylene and vinyl ester are reacted, the stirring power Pv per unit volume of the solution containing the vinyl ester in the polymerization tank is preferably 0.5 to 10 kW / m 3 The solution is stirred in a manner. The stirring power is less than 0.5 kW / m 3 In the case of , the amount of ethylene incorporated into the vinyl ester becomes insufficient, and the uniformity of the reaction liquid is also insufficient, and an ethylene-vinyl alcohol copolymer (A) having a block characteristic of ethylene units of 0.90 to 0.99 cannot be obtained. The stirring power is more preferably 1 kW / m 3 Above, further suitable for 1.5kW / m 3 On the other hand, the stirring power exceeds 10kW / m 3 In the case of , the power used for operation becomes very large, which is not preferred in industry. The stirring power is more suitable for 7kW / m 3 Below, further suitable for 5kW / m 3 The stirring power Pv per unit volume of the solution containing vinyl ester was measured by the method described in Examples described later.

[0084] The Froude number Fr is a ratio of inertial force to gravity, which is defined by the following equation, and serves as an index of the vortex shape on the liquid surface.

[0085] Fr=n 2 ×d / g

[0086] (In the formula, n is the rotation speed of the stirring blade (rps), d is the diameter of the stirring blade (m), and g is the acceleration due to gravity (m / s 2 )).

[0087] Preferably, when reacting ethylene with vinyl ester, the solution containing vinyl ester is stirred in a polymerization tank in such a manner that the Froude number Fr becomes 0.05 to 0.2. By adjusting the Froude number Fr within the above range and controlling the vortex shape of the liquid surface, the vinyl ester can be appropriately absorbed by ethylene, so it is considered that an ethylene-vinyl alcohol copolymer (A) having a block characteristic of ethylene units of 0.90 to 0.99 can be easily obtained. The Froude number Fr is more preferably greater than 0.06, and further preferably greater than 0.07. On the other hand, the Froude number Fr is more preferably less than 0.18, and further preferably less than 0.15. In order to make the Froude number Fr within the above range, it is only necessary to appropriately change the rotation speed of the stirring blade or the diameter of the stirring blade.

[0088] The stirring blade diameter d of the wide paddle is not particularly limited as long as it is adjusted in a manner that the stirring power Pv and the Froude number Fr are within the above range, but from the viewpoint of improving the ethylene absorption efficiency, it is preferably 0.5 to 5 m. The stirring blade diameter d is more preferably 0.75 m or more. On the other hand, the stirring blade diameter d is more preferably 4 m or less. The stirring blade diameter d is the value obtained by multiplying the distance from the rotation axis to the front end of the blade (the point farthest from the rotation axis) by 2 times.

[0089] The width b (length in the height direction) of the wide blade (paddle) is not particularly limited as long as it is adjusted according to the capacity of the polymerization tank 1, but is preferably 1 to 10 m from the viewpoint of improving ethylene absorption efficiency. The width b is more preferably 1.5 m or more. On the other hand, the width b is more preferably 8 m or less.

[0090] The ratio (b / d) of the width b of the wide blade (blade width) to the diameter d of the stirring blade can be determined according to the shape of the polymerization tank 1, etc., and is not particularly limited. From the viewpoint of improving the ethylene absorption efficiency, it is preferably 1 or more. The aforementioned ratio (b / d) is more preferably 1.5 or more. On the other hand, the aforementioned ratio (b / d) is usually 2.5 or less.

[0091] The shape of the polymerization tank 1 is not particularly limited, and a roughly cylindrical tank is generally used. In this case, the wide paddle is configured in a manner such that the rotation axis of the polymerization tank 1 is aligned with the rotation axis of the wide paddle in the roughly cylindrical polymerization tank 1. The ratio (d / D) of the diameter d (m) of the stirring blade to the inner diameter D (m) of the polymerization tank is not particularly limited as long as it does not hinder the effect of the present disclosure, and can be appropriately adjusted according to the polymerization tank used, but is generally 0.4 to 0.9. The capacity of the polymerization tank is not particularly limited, and is generally 1 to 200 kl.

[0092] The rotation speed n of the stirring blade can be adjusted in a manner that the stirring power Pv and the Froude number Fr are within the above ranges, and is not particularly limited, but is preferably 0.5 to 1.35 rps. When the rotation speed n is less than 0.5 rps, it is easy to supercool the polymerization solution near the heat transfer surface, so sometimes a gel-like substance is generated on the inner wall of the polymerization tank, making it difficult to operate for a long time. On the other hand, if the rotation speed n exceeds 1.35 rps, when a polymerization solution with low viscosity is used, the solution sometimes splashes and adheres to the inner wall of the gas phase portion of the polymerization tank. If such attachments solidify and mix into the polymerization solution, foreign matter is formed, so sometimes stable operation cannot be achieved.

[0093] In the past, when manufacturing ethylene-vinyl alcohol copolymer, the stirring power per unit volume as an index of stirring intensity can be controlled. However, stirring power is subject to various influences such as the shape of the capacity, viscosity and density of the reaction solution, the shape of the polymerization tank and the shape and rotating speed of the stirring wing. Therefore, only controlling the stirring power is difficult to highly control the blockiness of ethylene unit, resulting in the elongation of ethylene chain (blocking of ethylene unit), and the block characteristics of the ethylene unit in the ethylene-vinyl alcohol copolymer obtained are less than 0.90. On the other hand, in the case of carrying out polyreaction under specific conditions, the copolymer of ethylene chain shorter than in the past (the position of ethylene unit is random) can be obtained.

[0094] From the viewpoint of being able to more highly control the block characteristics of the ethylene unit, it is preferred that in the aforementioned production method, the aforementioned polymerization tank used in the polymerization step is connected to a heat exchanger via a pipe, wherein when obtaining an ethylene-vinyl ester copolymer, the following steps are further included: (b) a step of introducing the ethylene-containing gas present in the gas phase of the aforementioned polymerization tank into the aforementioned heat exchanger, (c) a step of supplying the ethylene ester to the aforementioned heat exchanger, (d) a step of contacting the ethylene ester with the ethylene-containing gas in the aforementioned heat exchanger, and (e) a step of extracting the ethylene-dissolved ethylene ester from the aforementioned heat exchanger and introducing it into the aforementioned polymerization tank. The ethylene ester may be directly supplied to the polymerization tank without passing through a heat exchanger, but by allowing the ethylene ester to absorb ethylene in the heat exchanger in advance and then supplying it to the polymerization tank, the ethylene ester can be effectively absorbed by the ethylene ester, so that the block characteristics of the ethylene unit can be highly controlled. It is also possible to allow a portion of the ethylene ester supplied to the polymerization tank to contact the ethylene-containing gas in the heat exchanger, but it is preferred that all of the supplied ethylene ester contact the ethylene-containing gas in the heat exchanger.

[0095] The heat exchanger used is not particularly limited, but from the viewpoint of efficiently absorbing ethylene, a heat exchanger with a large surface area is preferred. Examples thereof include a vertical wetted wall heat exchanger, a vertical wetted wall multi-tube heat exchanger, a packed tower type, or a heat exchanger provided with a jacket and / or coil in a porous plate or bubble-cap absorber, etc. Among them, a vertical wetted wall multi-tube heat exchanger is more preferred.

[0096] exist Figure 1 In the apparatus shown, a vertical wet wall multi-tube heat exchanger is used as the heat exchanger 2. The heat exchanger 2 is connected to a vinyl ester introduction pipe 10, through which vinyl ester is supplied to the upper part of the heat exchanger 2. As the raw material, vinyl ester may be used alone or in the form of a mixed solution containing the above-mentioned organic solvent and vinyl ester, but the latter is preferred.

[0097] Refrigerant pipes 11 and 12 are connected to Figure 1The heat exchanger 2 shown in the figure is connected to the refrigerant pipe 12. The position of the pipe is not limited to the one shown in the figure. The refrigerant is preferably supplied from the refrigerant pipe 12 connected to the lower part of the heat exchanger 2 and discharged from the refrigerant pipe 11 connected to the upper part of the heat exchanger 2. By connecting in this way, the vinyl ester can be effectively cooled and the ethylene absorption efficiency is good. The cooling medium is not particularly limited, and an alcohol aqueous solution such as methanol, ethanol, ethylene glycol, glycerin, an aqueous solution of salt or calcium chloride, Freon, etc. can be used. From the perspective of ease of operation and cost, an alcohol aqueous solution, especially a methanol aqueous solution, can be suitably used.

[0098] A gas discharge pipe 13 for discharging gas from the heat exchanger 2 is connected to the upper part of the heat exchanger 2. A mist separator (not shown) may also be connected to the gas discharge pipe 13. Liquid droplets in the discharged gas may be removed by the mist separator, and mist-free ethylene may be recovered or released. The mist separator is a device that separates liquid droplets floating in the gas by using external forces such as gravity, centrifugal force, electrostatic force, or by using a blocking or screening effect. Examples of the mist separator include a gravity settler, a cyclone, an electrostatic dust collector, a scrubber, a bag filter, and a packed layer. Among them, a cyclone separator is preferred.

[0099] The method for bringing vinyl ester into contact with ethylene-containing gas in the heat exchanger 2 is not particularly limited. For example, there may be mentioned a method in which vinyl ester is made to flow down from the upper part of the heat exchanger 2, and pressurized ethylene-containing gas is supplied to the lower part of the heat exchanger 2, and the two are brought into countercurrent contact in the heat exchanger 2; or a method in which vinyl ester is made to flow down from the upper part of the heat exchanger 2, and pressurized ethylene-containing gas is supplied to the upper part of the heat exchanger, and the two are brought into cocurrent contact in the heat exchanger 2. From the viewpoint of efficiently absorbing ethylene, the former is preferred.

[0100] exist Figure 1 In the apparatus shown, two conduits 3 and 4 connect a polymerization tank 1 and a heat exchanger 2. Ethylene-containing gas is introduced from the polymerization tank 1 to the lower portion of the heat exchanger 2 through the conduit 3, and vinyl ester that has absorbed ethylene is introduced from the lower portion of the heat exchanger 2 to the polymerization tank 1 through the conduit 4.

[0101] The vinyl ester is supplied to the heat exchanger 2 through the introduction pipe 10. The vinyl ester introduced into the upper portion of the heat exchanger 2 absorbs ethylene while passing through the heat exchanger 2.

[0102] The ethylene-containing gas is introduced into the heat exchanger 2 through the conduit 3 connected to the lower part of the heat exchanger 2. The conduit 3 on the heat exchanger side is connected to the lower part of the heat exchanger 2, and on the other hand, the vinyl ester introduction pipe 10 is connected to the upper part of the heat exchanger 2. The ethylene-containing gas rises in the heat exchanger 2 while countercurrently contacting the vinyl ester. As a result, the ethylene in the gas dissolves in the vinyl ester.

[0103] The vinyl ester that has absorbed ethylene is introduced into the polymerization tank 1 through the conduit 4. In the case of continuous production, ethylene circulates in the polymerization tank 1, the heat exchanger 2, and the conduits 3 and 4. Since a part of the ethylene is contained in the vinyl ester and discharged from the reaction solution outlet pipe 9, it is replenished from the ethylene supply source connected to the polymerization tank 1 through at least one of the conduits 5, 6, and 7.

[0104] [Cellulose nanofiber (CNF)]

[0105] The aqueous dispersion disclosed herein contains CNF.

[0106] By including CNF in the aqueous dispersion of the present invention, the film made using the aqueous dispersion of the present invention can suppress or improve water resistance, tensile elastic modulus and fracture stress reduction compared to the film made using the ethylene-vinyl alcohol copolymer (A) aqueous solution. At this time, the reduction in the fracture strain of the film is small. Such an effect is an effect of significantly reducing the fracture strain of the film made using the aqueous dispersion containing PVA and CNF to make a film compared to the effect of using the PVA aqueous solution to make a film.

[0107] In addition, the aqueous emulsion of the present disclosure contains CNF, and is excellent in heat-resistant adhesiveness and water resistance of the film.

[0108] The average fiber diameter of CNF contained in the aqueous dispersion and aqueous emulsion of the present disclosure is suitable for being 1 nm or more, more suitable for being 3 nm or more, and further suitable for being 4 nm or more. If the average fiber diameter is above the above lower limit, it is easy to manufacture. The above average fiber diameter is suitable for being 1000 nm or less, more suitable for being 500 nm or less, and further suitable for being 400 nm or less, and also preferably being 300 nm or less, 200 nm or less, or 100 nm or less. If the above average fiber diameter is below the above upper limit, when the aqueous dispersion or aqueous emulsion of the present disclosure is used to make a film, there is a tendency that the water resistance of the film is more excellent. It should be noted that in the present disclosure, the average fiber diameter of CNF is the number average fiber diameter calculated by microscopic observation. The number average fiber diameter can be calculated, for example, in the following manner: observe any 10 CNFs with a scanning electron microscope (SEM), and after obtaining the fiber diameter of CNF using analysis software for the observed image (SEM image), calculate the average value of the fiber diameters of 10 CNFs as the number average fiber diameter.

[0109] The average fiber length of CNF is suitable for being 0.01 μm or more, more suitable for being 0.1 μm or more, and further suitable for being 0.2 μm or more. If the average fiber length of CNF is above the above lower limit, when the aqueous dispersion or aqueous emulsion of the present invention is used to make a film, the tensile elastic modulus and the breaking point stress of the film tend to be further improved. The average fiber length of CNF is suitable for being 1000 μm or less, more suitable for being 500 μm or less, further suitable for being 100 μm or less, and particularly suitable for being 50 μm or less, and also preferably being 5 μm or less or 2 μm or less. If the average fiber length of CNF is below the above upper limit, when the aqueous dispersion or aqueous emulsion of the present invention is used to make a film, there is a tendency to suppress the breaking point strain of the film from being significantly reduced. If the above average fiber length is below the above upper limit, when the aqueous emulsion of the present invention is used to make a film, the water resistance of the film tends to be more excellent. In addition, in the present disclosure, the average fiber length of CNF is the number average fiber length calculated by microscopic observation. The number average fiber length can be calculated, for example, by observing any 10 CNFs with a scanning electron microscope (SEM), obtaining the fiber length of the CNFs from the observed image (SEM image) using analysis software, and then calculating the average value of the fiber lengths of the 10 CNFs as the number average fiber length.

[0110] The aspect ratio of CNF, that is, the ratio of the average fiber length to the average fiber diameter, is preferably 3 or more, more preferably 10 or more, and further preferably 50 or more. When the aspect ratio of CNF is above the above lower limit, when a film is produced using the aqueous dispersion or aqueous emulsion of the present disclosure, the tensile elastic modulus and the stress at break of the film tend to be further improved.

[0111] As CNF, for example, fibrillated cellulose fibers can be appropriately used. As raw materials for fibrillated cellulose fibers, for example, wood, straw, bamboo, bagasse, bamboo leaves, reeds or rice husks can be cited. Fibrillation can be performed by applying mechanical shearing force to cellulose fibers using a pulper or a homogenizer. In addition, the fibrillation of cellulose fibers can also be performed by chemical treatment. CNF may also contain lignin. Lignin is a component contained in the raw materials of fibrillated cellulose fibers. By adjusting the removal rate of lignin during fibrillation, its content can be adjusted. CNF can be a substance modified with anionic groups such as carboxyl groups and cationic groups, or it can be an unmodified substance. In a suitable embodiment, CNF can be listed as an aqueous dispersion of unmodified CNF. In other suitable embodiments, CNF can be listed as an aqueous emulsion of unmodified CNF.

[0112] [Aqueous dispersion]

[0113] In the present disclosure, aqueous dispersion refers to a dispersion in which CNF is dispersed in a medium containing water. The content of water contained in the above-mentioned medium is suitable for more than 40% by mass, more preferably more than 70% by mass, further suitable for more than 90% by mass, particularly suitable for more than 95% by mass, and can also be 100% by mass. The above-mentioned medium may also contain an organic solvent, and its content is suitable for less than 60% by mass, more preferably less than 30% by mass, further suitable for less than 10% by mass, and particularly suitable for less than 5% by mass.

[0114] In the aqueous dispersion of the present disclosure, preferably a part or all of the ethylene-vinyl alcohol copolymer (A) is dissolved, and more preferably substantially all of the ethylene-vinyl alcohol copolymer (A) is dissolved.

[0115] The content of CNF in the aqueous dispersion of the present invention is suitable for 0.1 mass parts or more, more suitable for 0.2 mass parts or more, further suitable for 0.3 mass parts or more, particularly suitable for 0.5 mass parts or more, and preferably 1 mass parts or more, 2 mass parts or more or 3 mass parts or more. If the content of CNF is above the above lower limit, in the case of using the aqueous dispersion of the present invention to make a film, the water resistance, tensile elastic modulus and breaking point stress of the film are further improved. In addition, if the content of CNF is above the above lower limit, the coating agent composed of the aqueous dispersion of the present invention can provide a coated paper with better water resistance, solvent barrier properties and oil resistance when bending, or a multilayer structure with better gas barrier properties when bending. The content of CNF in the aqueous dispersion of the present disclosure is suitable for less than 40 parts by mass, more preferably less than 30 parts by mass, further suitable for less than 25 parts by mass, relative to 100 parts by mass of ethylene-vinyl alcohol copolymer (A), and also preferably less than 20 parts by mass, less than 15 parts by mass, less than 13 parts by mass, less than 10 parts by mass or less than 8 parts by mass. If the content of CNF is below the above-mentioned upper limit, there is a tendency that the tensile elastic modulus is more excellent and the strain at the breaking point can be suppressed to be significantly reduced. In addition, the coating agent composed of the aqueous dispersion of the present disclosure has a fast drying speed when applied and a low viscosity, so it can be more suitable for making coated paper or a multilayer structure. The gas barrier properties of the multilayer structure made using the coating agent after bending load are more excellent.

[0116] The total content of ethylene-vinyl alcohol copolymer (A) and CNF in the aqueous dispersion of the present invention is suitable for 0.1% by mass or more, more suitable for 0.5% by mass or more, further suitable for 1% by mass or more, particularly suitable for 1.5% by mass or more, and preferably 2% by mass or more, 2.5% by mass or more, and 3% by mass or more. If the total content of ethylene-vinyl alcohol copolymer (A) and CNF is above the above lower limit, it is easy to make a film using the aqueous dispersion of the present invention. The total content of ethylene-vinyl alcohol copolymer (A) and CNF in the aqueous dispersion of the present invention is suitable for 30% by mass or less, more suitable for 27% by mass or less, further suitable for 23% by mass or less, particularly suitable for 20% by mass or less, and preferably 17% by mass or less, 15% by mass or less, 13% by mass or less, 10% by mass or less, or 8% by mass or less. If the total content of the above-mentioned ethylene-vinyl alcohol copolymer (A) and CNF is below the above upper limit, an appropriate viscosity can be maintained, so the aqueous dispersion is easy to handle.

[0117] The total content of the ethylene-vinyl alcohol copolymer (A) and CNF in the solid content contained in the aqueous dispersion of the present invention is preferably 55% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and preferably 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass. If the total content of the ethylene-vinyl alcohol copolymer (A) and CNF is above the above lower limit, the film strength of the film produced from the aqueous dispersion of the present invention is further excellent.

[0118] As long as it is within the scope that does not hinder the effect of the present disclosure, the aqueous dispersion of the present disclosure may also contain other ingredients other than ethylene-vinyl alcohol copolymer (A), CNF and water. As the above-mentioned other ingredients, resins, organic solvents, plasticizers, cross-linking agents, surfactants, anti-precipitants, thickeners, fluidity improvers, preservatives, adhesion improvers, antioxidants, penetrants, defoamers, fillers, wetting agents, colorants, adhesives, water-retaining agents, fillers, sugars such as starch and its derivatives, latex and other additives can be listed. They can be used alone or in combination of more than two. The content of the above-mentioned other ingredients in the aqueous dispersion of the present disclosure is suitable for less than 10% by mass, and it is also preferably less than 5% by mass, less than 2% by mass, less than 1% by mass or less than 0.5% by mass. The content of the above-mentioned other ingredients in the aqueous dispersion of the present disclosure, as long as the desired effect can be obtained, can be the amount in the aqueous dispersion as a whole, or can be the amount relative to the solid content in the aqueous dispersion. When the above-mentioned other components are resins other than the ethylene-vinyl alcohol copolymer (A), the content thereof is preferably 60% by mass or less, more preferably 50% by mass or less, and preferably 40% by mass or less, 30% by mass or less, 20% by mass or less, 10% by mass or less, or 5% by mass or less. As resins other than the above-mentioned ethylene-vinyl alcohol copolymer (A), for example, PVA (hereinafter sometimes referred to as "PVA (B)") substantially free of ethylene units, and polymers (C) containing ethylenically unsaturated monomer units described later, etc. can be cited.

[0119] The present disclosure includes an aqueous emulsion composed of an aqueous dispersion of the present disclosure. That is, as another embodiment of the present disclosure, an aqueous emulsion can be cited, which contains an ethylene-vinyl alcohol copolymer (A) and CNF, and the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%.

[0120] The method for producing the aqueous dispersion disclosed in the present invention is not particularly limited, and examples thereof include: (i) a method of adding CNF to an aqueous solution of ethylene-vinyl alcohol copolymer (A) and dispersing the CNF, (ii) a method of preparing an aqueous dispersion in which CNF is dispersed in water in advance, and mixing the aqueous dispersion with an aqueous solution of ethylene-vinyl alcohol copolymer (A), (iii) a method of adding ethylene-vinyl alcohol copolymer (A) to an aqueous dispersion in which CNF is dispersed in water, etc. Among them, from the viewpoint of reducing the undissolved components of the ethylene-vinyl alcohol copolymer (A) and dispersing the CNF more uniformly, (i) or (ii) is preferred.

[0121] In the above method (i) or (ii), the apparatus used in the step of dispersing CNF or in the step of mixing the aqueous dispersion of CNF and the aqueous solution of the ethylene-vinyl alcohol copolymer (A) includes, for example, a medium stirring type disperser, a high pressure disperser, and a rotary disperser.

[0122] [Water-based emulsion]

[0123] The aqueous emulsion of the present disclosure comprises an ethylene-vinyl alcohol copolymer (A) as a dispersant, a polymer (C) as a dispersoid, and CNF, wherein the content of the cellulose nanofibers is 0.1 to 40 parts by mass based on 100 parts by mass of the ethylene-vinyl alcohol copolymer (A).

[0124] Polymer (C) is a polymer containing ethylenically unsaturated monomer units. Examples of the above-mentioned ethylenically unsaturated monomers include vinyl ester monomers, olefin monomers, (meth) acrylic acid and its salts, (meth) acrylic acid ester monomers (monofunctional (meth) acrylic acid ester monomers, multifunctional (meth) acrylic acid ester monomers), (meth) acrylamide monomers, vinyl ether monomers, nitrile monomers, allyl monomers, α, β-unsaturated mono- or dicarboxylic acid monomers, diene monomers, aromatic vinyl monomers (e.g., styrene monomers, condensed polycyclic aromatic monomers), heterocyclic vinyl monomers, etc. Among them, preferably at least one selected from vinyl ester monomers, (meth) acrylic acid ester monomers, styrene monomers and diene monomers, more preferably vinyl ester monomers. They may be used alone or in combination of two or more. In addition, in the present disclosure, "(meth) acrylic acid" refers to one or more selected from acrylic acid and methacrylic acid.

[0125] Examples of the vinyl ester monomer include vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl cinnamate, vinyl crotonate, vinyl decanoate, vinyl hexanoate, vinyl octanoate, vinyl isononanoate, vinyl trimethylacetate, vinyl 4-tert-butylbenzoate, vinyl 2-ethylhexanoate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, and vinyl benzoate. Among them, vinyl acetate is preferred from an industrial point of view.

[0126] Examples of the olefin monomer include ethylene and propylene.

[0127] Examples of (meth)acrylic acid and salts thereof include acrylic acid, methacrylic acid, sodium salts thereof, and potassium salts thereof.

[0128] Examples of the monofunctional (meth)acrylate monomer include (meth)acrylic acid and salts thereof, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate.

[0129] Examples of the polyfunctional (meth)acrylate monomer include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol hexa(meth)acrylate, and trimethylolpropane tri(meth)acrylate.

[0130] Examples of the (meth)acrylamide monomer include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, diacetone(meth)acrylamide, (meth)acrylamidepropanesulfonic acid and salts thereof, (meth)acrylamidepropyldimethylamine and salts thereof or quaternary ammonium salts thereof, N-hydroxymethyl(meth)acrylamide and derivatives thereof, and the like.

[0131] Examples of the vinyl ether monomer include methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether.

[0132] Examples of the nitrile monomer include acrylonitrile and methacrylonitrile.

[0133] Examples of the allyl monomer include allyl acetate and allyl chloride.

[0134] Examples of the α,β-unsaturated mono- or dicarboxylic acid monomers include aliphatic unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid, and salts or esters thereof.

[0135] Examples of the diene monomer include butadiene, isoprene, and chloroprene.

[0136] Examples of the aromatic vinyl monomer include styrene monomers such as styrene, α-methylstyrene, p-methylstyrene, chlorostyrene, α-butoxystyrene, 1-ethyl-2-vinylbenzene, and vinylbiphenyl; and condensed polycyclic aromatic monomers such as vinylnaphthalene. Preferred examples include styrene monomers.

[0137] Examples of the heterocyclic vinyl monomer include N-vinyl-2-pyrrolidone and the like.

[0138] The content of the ethylenically unsaturated monomer units relative to all monomer units of the polymer (C) is preferably 70% by mass or more, and may be 80% by mass or more, 90% by mass or more, or 95% by mass or more, and may be 100% by mass. If the content of the ethylenically unsaturated monomer units is above the above lower limit, the emulsion polymerization stability of the ethylene-vinyl alcohol copolymer (A) is further excellent.

[0139] The content of CNF in the aqueous emulsion of the present disclosure is suitable for 0.15 mass parts or more, more suitable for 0.2 mass parts or more, further suitable for 0.3 mass parts or more, particularly suitable for 0.5 mass parts or more, and preferably 1 mass part or more, 2 mass parts or more, 3 mass parts or more or 5 mass parts or more. If the content of CNF is above the above lower limit, the heat-resistant adhesiveness and water resistance of the aqueous emulsion of the present disclosure are more excellent. The content of CNF in the aqueous emulsion of the present disclosure is suitable for 38 mass parts or less, more suitable for 35 mass parts or less, and preferably 30 mass parts or less, 25 mass parts or less or 20 mass parts or less, relative to 100 mass parts of ethylene-vinyl alcohol copolymer (A). If the content of CNF is below the above upper limit, the heat-resistant adhesiveness and water resistance of the aqueous emulsion of the present disclosure and the water resistance of the film are more excellent.

[0140] The total content of the ethylene-vinyl alcohol copolymer (A) and CNF in the aqueous emulsion of the present invention is suitable for being 2 parts by mass or more, more suitable for being 2.5 parts by mass or more, and further suitable for being 3 parts by mass or more, relative to 100 parts by mass of the polymer (C), and there is also a case where it is preferably 4 parts by mass or more or 5 parts by mass or more. If the total content of the ethylene-vinyl alcohol copolymer (A) and CNF is above the above lower limit, the heat-resistant adhesiveness of the aqueous emulsion of the present invention is more excellent. The total content of the ethylene-vinyl alcohol copolymer (A) and CNF in the aqueous emulsion of the present invention is suitable for being 35 parts by mass or less, more suitable for being 30 parts by mass or less, and further suitable for being 25 parts by mass or less, relative to 100 parts by mass of the polymer (C). If the total content of the above-mentioned ethylene-vinyl alcohol copolymer (A) and CNF is below the above upper limit, the water resistance of the film of the aqueous emulsion of the present invention is more excellent.

[0141] The solid content concentration in the aqueous emulsion is preferably 10 to 80% by mass. When the solid content concentration is 10% by mass or more, the viscosity of the aqueous emulsion will not become too low, and the particles are not easy to precipitate. The solid content concentration is more preferably 15% by mass or more, and it is also preferably 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more, or 40% by mass or more. On the other hand, if the solid content concentration is below 80% by mass, it is not easy to generate agglomerates in emulsion polymerization, and manufacturing becomes easy. The solid content concentration is more preferably 75% by mass or less, and it is also preferably 70% by mass or less, 65% by mass or less, or 60% by mass or less. Here, the solid content means the total amount of dry solid matter contained in the aqueous emulsion, that is, the total amount of solid matter remaining when the medium such as water is removed.

[0142] The total content of the ethylene-vinyl alcohol copolymer (A), polymer (C) and CNF in the solid content contained in the aqueous emulsion of the present disclosure is preferably 55% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and preferably 90% by mass or more, 95% by mass or more, 99% by mass or more or 100% by mass. If the total content of the ethylene-vinyl alcohol copolymer (A), polymer (C) and CNF is above the above lower limit, the film strength is excellent.

[0143] The dispersant may further contain PVA that does not substantially contain ethylene units (hereinafter sometimes referred to as "PVA (B)"). The appropriate viscosity-average degree of polymerization and saponification degree of PVA (B) are the same as those of the aforementioned ethylene-vinyl alcohol copolymer (A). PVA (B) may be unmodified PVA or modified PVA. Examples of modified PVA include anionic modified PVAs such as sulfonic acid group-modified PVA and carboxylic acid group-modified PVA; cationic modified PVAs such as quaternary ammonium group-modified PVA; amide-modified PVA; polyoxyalkylene-modified PVA; acetoacetyl-modified PVA; diacetone acrylamide-modified PVA, and the like.

[0144] The content of water contained in the medium of the aqueous emulsion of the present disclosure is preferably 40% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may be 100% by mass. The above-mentioned medium may also contain an organic solvent, but its content is preferably 60% by mass or less, more preferably 30% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less.

[0145] As long as it is not hindering the scope of the effect of the present disclosure, the aqueous emulsion of the present disclosure may also contain other ingredients other than ethylene-vinyl alcohol copolymer (A), polymer (C), CNF and water. As the above-mentioned other ingredients, resins, organic solvents, plasticizers, cross-linking agents, surfactants, anti-precipitants, thickeners, fluidity improvers, preservatives, adhesion improvers, antioxidants, impregnants, defoamers, fillers, wetting agents, colorants, adhesives, water-retaining agents, fillers, sugars such as starch and its derivatives, latex additives, etc. other than ethylene-vinyl alcohol copolymer (A) and polymer (C) can be listed. They can be used alone as one, or two or more can be used in combination. The content of the above-mentioned other ingredients in the aqueous emulsion of the present disclosure is suitable for less than 15% by mass, more preferably less than 10% by mass, and also has preferably less than 5% by mass, less than 2% by mass, less than 1% by mass or less than 0.5% by mass.

[0146] [Method for producing aqueous emulsion]

[0147] The present disclosure provides a method for producing an aqueous emulsion of the present disclosure. The method for producing an aqueous emulsion of the present disclosure is preferably a method having a step (1) of emulsion-polymerizing an ethylenically unsaturated monomer in the presence of an ethylene-vinyl alcohol copolymer (A) to obtain an aqueous emulsion (hereinafter sometimes referred to as "aqueous emulsion without CNF addition") and a step (2) of blending CNF into the aqueous emulsion, or a method having a step (3) of obtaining an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and CNF and a step (4) of mixing the aqueous dispersion with an ethylenically unsaturated monomer and performing emulsion polymerization.

[0148] Step (2) is preferably carried out by adding an aqueous dispersion of CNF to the aqueous emulsion obtained in step (1) without adding CNF and mixing. Step (3) is preferably carried out by the following methods: a method of adding CNF to an aqueous solution of ethylene-vinyl alcohol copolymer (A) and dispersing it, a method of mixing an aqueous solution of ethylene-vinyl alcohol copolymer (A) and an aqueous dispersion of CNF, a method of dissolving ethylene-vinyl alcohol copolymer (A) in an aqueous dispersion of CNF, or a method of adding ethylene-vinyl alcohol copolymer (A) and CNF to water at one time and simultaneously dissolving ethylene-vinyl alcohol copolymer (A) and dispersing CNF. The aqueous dispersion of the starting material used for steps (2) and (3) contains CNF. In addition to CNF and water, the aqueous dispersion may also contain other components of the aqueous emulsion of the present disclosure in the aforementioned types and amounts. Among these methods, as a method for obtaining an aqueous dispersion containing CNF, for example, a method of mixing water and CNF and dispersing using a medium stirring type disperser, a high-pressure disperser or a rotary disperser can be cited.

[0149] As the ethylenically unsaturated monomer used in the step (1) and the step (4), the above-mentioned monomers as examples of the ethylenically unsaturated monomer contained in the polymer (C) can be mentioned.

[0150] As a method for obtaining an aqueous emulsion in step (1), there can be cited a method in which, after charging a dispersant and an ethylenically unsaturated monomer, a suitably selected polymerization initiator is added to emulsion polymerize the monomer. There are no particular limitations on the method for charging and adding the dispersant, and examples include a method in which the dispersant is charged all at once in the initial stage, a method in which the dispersant is continuously added during the polymerization, and the like. Among these, from the viewpoint of increasing the grafting rate of the ethylene-vinyl alcohol copolymer (A) and any PVA (B) included with respect to the dispersant, a method in which the dispersant is charged all at once in the initial stage into the polymerization system is preferred. In these methods, the polymerization reaction can be adjusted by appropriately adjusting the amount of the dispersant, the amount of the ethylenically unsaturated monomer, and the amount of the solvent.

[0151] As a method for carrying out emulsion polymerization in step (4), there can be mentioned a method in which an ethylenically unsaturated monomer and an appropriately selected polymerization initiator are added to the aqueous dispersion obtained in step (3) to carry out emulsion polymerization of the monomer. In the above method, the polymerization reaction can be adjusted by appropriately adjusting the amount of the dispersant, the amount of the ethylenically unsaturated monomer, and the amount of the solvent.

[0152] The amount of the dispersant used relative to 100 parts by mass of polymer (C) is not particularly limited, and is preferably more than 2 parts by mass and less than 35 parts by mass. The amount used is more preferably more than 2.5 parts by mass, and is also preferably more than 3 parts by mass, more than 4 parts by mass or more than 5 parts by mass. When the amount of the dispersant used is more than the above lower limit, the emulsion polymerization reaction is easily stabilized. The amount of the above dispersant used is more preferably less than 30 parts by mass, and is also preferably less than 25 parts by mass, less than 20 parts by mass or less than 15 parts by mass. When the amount of the dispersant used is less than the above upper limit, when using an aqueous emulsion as an adhesive, there is a tendency that the heat-resistant adhesiveness of the adhesive is excellent. Here, in the present disclosure, when a monomer is subjected to emulsion polymerization to manufacture an aqueous emulsion in the presence of a dispersant, the monomer is almost entirely polymerized to become a polymer (C). Therefore, the amount of the monomer remaining in the aqueous emulsion is a very small amount, which can be ignored.

[0153] In the emulsion polymerization, as the polymerization initiator, a water-soluble single initiator or a water-soluble redox initiator commonly used in emulsion polymerization can be used. One of these polymerization initiators can be used alone, or two or more can be used in combination. Among them, a redox initiator is preferred.

[0154] Examples of the water-soluble single initiator include azo initiators, hydrogen peroxide, peroxides such as persulfates (potassium, sodium or ammonium salts), etc. Examples of the azo initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile).

[0155] As a redox initiator, a substance composed of a combination of an oxidizing agent and a reducing agent can be used. As the oxidizing agent, peroxide is preferred. As the reducing agent, metal ions, reducing compounds, etc. can be listed. As a combination of an oxidizing agent and a reducing agent, a combination of peroxide and metal ions, a combination of peroxide and reducing compounds, and a substance composed of a combination of peroxide, metal ions and reducing compounds can be listed. As peroxides, hydrogen peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and other hydroperoxides, persulfates (potassium, sodium or ammonium salts), tert-butyl peracetate, peresters (tert-butyl perbenzoate), etc. can be listed. As metal ions, Fe 2+ Cr 2+ 、V 2+ 、Co 2+ 、Ti 3+ , Cu + etc. can accept a metal ion that moves one electron. As reducing compounds, sodium bisulfite, sodium bicarbonate, tartaric acid, fructose, dextrose, sorbitol, rongalite, ascorbic acid can be cited. Among these, preferably, a combination of one or more oxidizing agents selected from hydrogen peroxide, potassium persulfate, sodium persulfate and ammonium persulfate, and one or more reducing agents selected from sodium bisulfite, sodium bicarbonate, tartaric acid, rongalite and ascorbic acid, more preferably a combination of hydrogen peroxide and one or more reducing agents selected from sodium bisulfite, sodium bicarbonate, tartaric acid, rongalite and ascorbic acid.

[0156] When the emulsion polymerization is performed, an alkali metal compound, a surfactant, a buffer, a polymerization degree adjuster, and the like may be appropriately used within a range not impairing the effects of the present disclosure.

[0157] As the alkali metal compound, there is no particular limitation as long as it contains an alkali metal (sodium, potassium, rubidium, cesium), and it can be an alkali metal ion itself or a compound containing an alkali metal. As the compound containing an alkali metal, for example, weakly basic alkali metal salts such as alkali metal carbonates, alkali metal acetates, alkali metal bicarbonates, alkali metal phosphates, alkali metal sulfates, alkali metal halide salts, and alkali metal nitrates; strongly basic alkali metal compounds such as alkali metal hydroxides and alkali metal alkoxides, etc. These alkali metal compounds can be used alone or in combination of two or more.

[0158] As weakly basic alkali metal salts, for example, alkali metal carbonates such as sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate can be listed; alkali metal bicarbonates such as sodium bicarbonate and potassium bicarbonate; alkali metal phosphates such as sodium phosphate and potassium phosphate; alkali metal carboxylates such as sodium acetate, potassium acetate, and cesium acetate; alkali metal sulfates such as sodium sulfate, potassium sulfate, and cesium sulfate; alkali metal halide salts such as cesium chloride, cesium iodide, potassium chloride, and sodium chloride; alkali metal nitrates such as sodium nitrate, potassium nitrate, and cesium nitrate. Among them, from the point of view of alkalinity in the emulsion, it is preferably an alkali metal carboxylate, alkali metal carbonate, and alkali metal bicarbonate that can act as a salt of a weak acid and a strong base during dissociation, and more preferably an alkali metal carboxylate. By using these weakly basic alkali metal salts, the weakly basic alkali metal salt acts as a pH buffer in the emulsion polymerization, thereby enabling the emulsion polymerization to proceed stably.

[0159] The content of the alkali metal compound (alkaline metal conversion) can be appropriately selected according to the type of alkali metal compound used, but the content of the alkali metal compound (alkaline metal conversion) relative to the total mass of the aqueous emulsion (solid conversion) is preferably 100 to 15000 ppm, more preferably 120 to 12000 ppm, and further preferably 150 to 8000 ppm. If the content of the alkali metal compound is above 100 ppm, the stability of the emulsion polymerization of the aqueous emulsion tends to be excellent, and if it is below 15000 ppm, it is easy to suppress the coloring of the film formed by the aqueous emulsion. It should be noted that the content of the alkali metal compound can be measured by an ICP emission spectrometer or the like. Here, "ppm" means "mass ppm".

[0160] As a surfactant, any one of a nonionic surfactant, an anionic surfactant and a cationic surfactant can be used. As a nonionic surfactant, for example, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene fatty acid ester, polyoxyalkylene alkyl ether, polyoxyethylene derivative, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitol fatty acid ester, glycerol fatty acid ester, etc. can be cited. As an anionic surfactant, for example, alkyl sulfate, alkyl aryl sulfate, alkyl sulfonate, sulfuric acid ester of hydroxyl alkanol, dialkyl sulfosuccinate salt, sulfuric acid ester and phosphate ester of alkyl or alkyl aryl polyethoxy alkanol, etc. can be cited. As a cationic surfactant, for example, alkylamine salt, quaternary ammonium salt, polyoxyethylene alkylamine, etc. can be cited. The amount of surfactant used is preferably less than 2% by mass relative to the total amount of ethylenic unsaturated monomers. If the amount of surfactant used is less than 2% by mass, then when an aqueous emulsion is used to make a film, the water resistance of the film is more excellent.

[0161] Examples of the buffer include acids such as acetic acid, hydrochloric acid, and sulfuric acid; bases such as ammonia, amines, caustic soda, caustic potash, and calcium hydroxide; or alkali metal carbonates, phosphates, and acetates. Examples of the polymerization degree adjuster include mercaptans and alcohols.

[0162] The dispersion medium in the above-mentioned emulsion polymerization is preferably an aqueous medium with water as the main component. The aqueous medium with water as the main component may also contain a water-soluble organic solvent (alcohols, ketones, etc.) soluble in water in any proportion. Here, "aqueous medium with water as the main component" is a dispersion medium containing 50% by mass or more of water. From the viewpoint of cost and environmental load, the dispersion medium is preferably an aqueous medium containing 90% by mass or more of water, more preferably water. In the above-mentioned method for manufacturing an aqueous emulsion, it is preferred that before the emulsion polymerization is initiated, the above-mentioned dispersant is dissolved in the dispersion medium and heated, and then cooled and nitrogen replaced. At this time, the heating temperature is preferably 80 to 100°C. The temperature of the emulsion polymerization is preferably about 20 to 95°C, more preferably about 40 to 90°C.

[0163] The aqueous emulsion of the present disclosure is suitable for use as an adhesive. That is, the present disclosure discloses an adhesive composed of the aqueous emulsion of the present disclosure. The adhesive can be used for woodworking, paper processing, etc. In addition, the aqueous emulsion of the present disclosure can be used for a wide range of purposes such as coatings, fiber processing, inorganic adhesives, cement admixtures, mortar primers, etc. The aqueous emulsion of the present disclosure can also be powdered by spray drying, etc., and thus used as a so-called powder emulsion.

[0164] [membrane]

[0165] The present disclosure also provides a film formed from the aqueous dispersion or aqueous emulsion of the present disclosure. The thickness of the film is not particularly limited, but is preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and preferably 1000 μm or less, more preferably 500 μm or less, and further preferably 200 μm or less.

[0166] As the manufacturing method of the above-mentioned film, for example, a casting film method, a coating method, a wet film method, a gel film method, etc. can be cited. In the case of making a film by a casting film method, if hot air is used for drying, the surface is dried to produce a film, and sometimes problems such as uneven drying and bubble incorporation (bubble) occur. Therefore, it is preferred that the aqueous dispersion disclosed in the present invention is cast on a glass plate or a plastic film such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and dried to form a film. There is no particular restriction on the drying conditions, for example, it can be dried at 10 to 40 degrees and 30 to 80% RH for 6 hours to 2 weeks. The film obtained by the above-mentioned manufacturing method is a film containing an ethylene-vinyl alcohol copolymer (A), CNF and any polymer (C) contained. The film can also be a gas barrier film.

[0167] [Coating agent]

[0168] The aqueous dispersion and aqueous emulsion of the present disclosure can also be used as a coating agent (i.e., a coating liquid). That is, the present disclosure provides a coating agent composed of the aqueous dispersion or aqueous emulsion of the present disclosure. The substrate on which the coating agent of the present disclosure is applied is not particularly limited, and examples thereof include paper, a substrate containing a resin, and the like. As the coating agent, the aqueous dispersion or aqueous emulsion of the present disclosure can be used directly, or other components can be further added for use. As the above-mentioned other components, the above-mentioned components other than the ethylene-vinyl alcohol copolymer (A), CNF, and water can be listed. In addition, as the above-mentioned other components, water-resistant agents such as glyoxal, urea resin, melamine resin, polyvalent metal salt, and water-soluble polyamide resin can also be listed; pH adjusters such as ammonia, caustic soda, sodium carbonate, and phosphoric acid; mold release agents; colorants such as pigments; various modified PVAs such as unmodified PVA, carboxyl-modified PVA, sulfonic acid-modified PVA, acrylamide-modified PVA, cationic-modified PVA, and long-chain alkyl-modified PVA; casein, raw starch (wheat, corn, rice, potato, sugar cane, cassava, sago), raw starch decomposition products (dextrin, etc.), starch derivatives ( Water-soluble polymers such as oxidized starch, etherified starch, esterified starch, cationic starch, etc.), seaweed polysaccharides (sodium alginate, carrageenan, agar (agarose, agaropectin), furcellaran, etc.), water-soluble cellulose derivatives (carboxyalkyl cellulose, alkyl cellulose, hydroxyalkyl cellulose, etc.); synthetic resin emulsions such as styrene-butadiene copolymer latex, polyacrylate emulsion, vinyl acetate-ethylene copolymer emulsion, vinyl acetate-acrylate copolymer emulsion, etc.

[0169] [Paper coating agent]

[0170] The coating agent of the present disclosure may be a paper coating agent (ie, a coating liquid for paper).

[0171] The concentration of the ethylene-vinyl alcohol copolymer (A) in the paper coating agent can be arbitrarily selected depending on the coating amount (increase in dry mass of paper caused by coating), the device used for coating, operating conditions, etc., and is preferably 1.0 to 30% by mass, and more preferably 2.0 to 25.0% by mass.

[0172] As a method for applying the paper coating agent of the present invention to paper, known methods can be cited, such as a method of applying it to one or both sides of the paper using a sizing machine, a gate roll coater, a SYM sizing machine, a rod coater, a curtain coater, etc., or a method of impregnating the paper with a coating liquid. The coated paper can be dried by a known method, such as hot air, infrared rays, a heating cylinder, or a combination of these. The dried coated paper can be further improved in barrier properties by humidity adjustment and calendering. As calendering treatment conditions, it is preferred that the roller temperature is room temperature to 100°C and the roller line pressure is 20 to 300 kg / cm.

[0173] As another embodiment of the present disclosure, there can be cited coated paper having paper and coated with the paper coating agent of the present disclosure on the aforementioned paper. The coated paper formed using the paper coating liquid of the present disclosure can be used as a release paper base paper, oil-resistant paper, gas-barrier paper, thermal paper, inkjet paper, pressure-sensitive paper, etc. Among them, release paper base paper or oil-resistant paper is preferred. That is, the present disclosure provides the above-mentioned coated paper as a release paper base paper or oil-resistant paper.

[0174] The release paper base paper has a filling layer (barrier layer) formed by a paper coating liquid on a substrate (paper). Examples of the substrate (paper) include thick paper such as manila board, white chipboard, and liner paper; general high-quality paper, medium-quality paper, gravure paper and other printing papers. The release paper has a release layer, which is laminated on the filling layer of the release paper base paper. The release layer is preferably composed of a silicone resin. Examples of the silicone resin include well-known silicone resins, such as solvent-based silicones, solvent-free silicones, and emulsion-based silicones. The coating amount in the release paper base paper (the increase in the dry mass of the paper caused by coating) is not particularly limited, and is, for example, 0.1 to 2.0 g / m 2 .

[0175] Oil-resistant paper has an oil-resistant layer formed by a paper coating liquid on a substrate (paper). Examples of the substrate (paper) include thick paper such as manila board, white board, and liner paper; printing paper such as general top-grade paper, medium-grade paper, and gravure paper; kraft paper, glass paper, and parchment paper. The coating amount (increase in dry mass of paper caused by coating) in oil-resistant paper is not particularly limited, and is, for example, 0.1 to 20 g / m 2 .

[0176] [Multilayer structure]

[0177] Another embodiment of the present disclosure includes a multilayer structure having a substrate containing a resin and a coating agent of the present disclosure applied thereon. The multilayer structure has a layer (1) formed of the coating agent of the present disclosure and a layer (2) as a substrate containing a resin.

[0178] The layer (1) contains an ethylene-vinyl alcohol copolymer (A) and CNF. The total content of the ethylene-vinyl alcohol copolymer (A) and CNF in the layer (1) is preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 95% by mass or more, and may be 100% by mass.

[0179] The resin contained in the layer (2) is preferably at least one selected from the group consisting of polyolefin resins, polyester resins and polyamide resins.

[0180] Examples of the polyolefin resin include polyethylene [high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (VLDPE), etc.], polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylate copolymer, etc. Among them, polyethylene and polypropylene are preferred.

[0181] Examples of the polyester resin include PET, polyethylene naphthalate, polybutylene terephthalate, polyethylene terephthalate / isophthalate, etc. Among them, PET is preferred.

[0182] Examples of the polyamide resin include homopolymers such as polycaproamide (nylon-6), polyundecanamide (nylon-11), polylaurolactam (nylon-12), polyhexamethylene adipamide (nylon-6,6), and polyhexamethylene sebacamide (nylon-6,12); caprolactam / laurolactam copolymer (nylon-6 / 12), caprolactam / aminoundecanoic acid polymer (nylon-6 / 11), caprolactam / ω-aminononanoic acid polymer (nylon-6,9), caprolactam / hexamethylenediammonium adipate copolymer (nylon-6 / 6,6), caprolactam / hexamethylenediammonium adipate / hexamethylenediammonium sebacate copolymer (nylon-6 / 6,6 / 6,12), polymers of adipic acid and meta-xylylenediamine, and polymers of hexamethylenediamine and iso-terephthalic acid, i.e., copolymers of aromatic nylons. Among them, polycaproamide (nylon-6) and polyhexamethylene adipamide (nylon-6,6) are preferred.

[0183] The content of the polyolefin resin, polyester resin and polyamide resin contained in the layer (2) is preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 95% by mass or more, and may be 100% by mass.

[0184] The thickness of layer (1) is preferably 0.01 μm or more, more preferably 0.1 μm or more. The thickness of layer (1) is preferably 100 μm or less, more preferably 50 μm or less, and preferably 20 μm or less or 9 μm or less. The thickness of layer (2) is preferably 5 to 100 μm. The ratio of the thickness of layer (1) to the thickness of layer (2) is preferably 0.9 or less, more preferably 0.5 or less. The above thickness ratio is preferably 0.01 or more. These thicknesses refer to the final thickness when the film is stretched.

[0185] In order to improve the gas barrier properties, strength and operability, the layers (1) and (2) may also contain inorganic layered compounds. Examples of inorganic layered compounds include micas, talc, montmorillonite, kaolinite and vermiculite, which may be naturally occurring or synthetic.

[0186] For the purpose of improving water resistance, the layer (1) and the layer (2) may contain a crosslinking agent. Examples of the crosslinking agent include epoxides, isocyanate compounds, aldehyde compounds, titanium compounds, silica compounds, aluminum compounds, zirconium compounds, boron compounds, etc. Among them, colloidal silica, silica compounds such as alkyl silicate are preferred.

[0187] The multilayer structure disclosed in the present invention may have an adhesive component layer between layer (1) and layer (2) for the purpose of improving adhesion. Examples of the adhesive component include anchor coating agents, etc. The adhesive component layer may be formed by applying the adhesive component to the surface of the substrate before applying the aqueous dispersion to the substrate.

[0188] The multilayer structure of the present disclosure may further have a heat-seal resin layer on the surface of layer (1) that is not in contact with layer (2). The heat-seal resin layer is usually formed by extrusion lamination or dry lamination. Examples of the heat-seal resin include polyethylene resins such as HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene / α-olefin random copolymers, and ionomer resins.

[0189] As a method for producing the multilayer structure of the present invention, for example, a method in which the aqueous dispersion of the present invention is applied on the surface of a substrate containing a resin other than the ethylene-vinyl alcohol copolymer (A) contained in the layer (2), and then the medium of the aqueous dispersion is removed. The temperature when the aqueous dispersion is applied is preferably 20 to 80°C. The coating method can appropriately use a gravure roll coating method, a reverse gravure coating method, a reverse roll coating method, or a wire rod coating method. The substrate or the obtained multilayer structure before the aqueous dispersion is applied may also be stretched or heat-treated. In this case, if workability is considered, it is preferably a method in which the substrate is stretched in one stage, the aqueous dispersion is applied on the substrate, and then stretched in two stages, and heat-treated during or after the two stages. The heat treatment is performed in air, etc. The heat treatment temperature can be adjusted according to the type of the substrate, and is usually 140°C to 170°C in the case of a polyolefin film and 140°C to 240°C in the case of a polyester film and a polyamide film. When heat treatment of layer (1) is performed, it is usually performed simultaneously with heat treatment of layer (2).

[0190] The multilayer structure of the present disclosure can be used as a gas barrier film. The gas barrier film can be used as a packaging material. That is, as other embodiments of the present disclosure, packaging materials having the multilayer structure of the present disclosure can be listed. The packaging material can be used to package, for example, food; beverages; pesticides, pharmaceuticals, and other drugs; medical equipment; industrial materials such as mechanical parts and precision materials; clothing, etc. In particular, the packaging material can be preferably used for applications that require barrier properties to oxygen and for applications where the interior of the packaging material is replaced with various functional gases. Examples of the form of the packaging material include vertical form fill seal bags, vacuum packaging bags, pouches with spouts, laminated tube containers, and container covers.

[0191] [Adhesive]

[0192] The aqueous dispersion and aqueous emulsion of the present disclosure can also be used as adhesives. That is, as other embodiments of the present disclosure, adhesives containing the aqueous dispersion or aqueous emulsion of the present disclosure can be listed. The adhesive can directly use the aqueous dispersion or aqueous emulsion of the present disclosure, or can further add other components and use. As the above-mentioned other components, the above-mentioned components other than ethylene-vinyl alcohol copolymer (A), polymer (C), CNF and water can be listed. Among them, there is a case where a plasticizer or a cross-linking agent is preferably added.

[0193] Examples of the plasticizer include dicarboxylic acid ester compounds and aryloxy group-containing compounds.

[0194] Examples of the dicarboxylic acid ester compound include 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, methyl adipate, dimethyl succinate, dimethyl glutarate, dibutyl phthalate, diphenyl phthalate, dihexyl phthalate, dicyclohexyl phthalate, dihydroabietyl phthalate, and dimethyl isophthalate.

[0195] As the aryloxy group in the aryloxy group-containing compound, phenoxy group and substituted phenoxy group can be mentioned. As the substituted phenoxy group, alkoxyphenoxy group having 1 to 12 carbon atoms, alkylphenoxy group having 1 to 12 carbon atoms, etc. can be mentioned. The number of substituents is not particularly limited, and is preferably 1 to 5, and more preferably 1 to 3. As the aryloxy group-containing compound, a compound containing a substituted or unsubstituted phenoxy group is preferred, and a compound containing a substituted or unsubstituted phenoxy group that does not contain a vinyl group is more preferred. As specific examples of compounds containing aryloxy groups, phenoxyethanol, ethylene glycol monophenyl ether, polypropylene glycol monophenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene dinonylphenyl ether, etc. can be mentioned. The plasticizer can be used alone or in combination of two or more.

[0196] The content of the plasticizer is preferably 0.5 to 20 parts by mass, more preferably 1.0 to 10 parts by mass, based on 100 parts by mass of the solid content in the aqueous dispersion or aqueous emulsion. When the content of the plasticizer is within the above range, an adhesive having better adhesiveness can be obtained.

[0197] Examples of the crosslinking agent include polyvalent isocyanate compounds; hydrazine compounds; polyamide polyamine epichlorohydrin resins (PAE); water-soluble aluminum salts such as aluminum chloride and aluminum nitrate; and glyoxal resins such as urea-glyoxal resins.

[0198] The polyvalent isocyanate compound is a compound having two or more isocyanate groups in the molecule. Examples of the polyvalent isocyanate compound include toluene diisocyanate (TDI), hydrogenated TDI, trimethylolpropane-TDI adduct (e.g., "Desmodur L" of Bayer), triphenylmethane triisocyanate, methylene diphenyl isocyanate (MDI), polymethylene polyphenyl polyisocyanate (PMDI), hydrogenated MDI, polymerized MDI, hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI), 4,4-dicyclohexylmethane diisocyanate, isophorone diisocyanate (IPDI), etc. As the polyvalent isocyanate compound, a prepolymer having an isocyanate group at the terminal group obtained by prepolymerizing a polyol with an excess of polyisocyanate can also be used.

[0199] Hydrazine compounds are compounds having a hydrazine group (H2N-NH-) in the molecule. Examples of hydrazine compounds include hydrazine, hydrazine hydrate, inorganic salts of hydrazine such as hydrochloric acid, sulfuric acid, nitric acid, sulfurous acid, phosphoric acid, thiocyanic acid, and carbonic acid, and organic salts such as formic acid and oxalic acid; monosubstituted hydrazine such as methylhydrazine, ethylhydrazine, propylhydrazine, butylhydrazine, and allylhydrazine; symmetrical disubstituted hydrazine such as 1,1-dimethylhydrazine, 1,1-diethylhydrazine, and (1-butyl-2-methylhydrazine); and the like. Furthermore, various compounds known in the past such as polyhydrazide compounds such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, adipic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycolic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, dimer acid dihydrazide, etc. can be used. Among them, adipic acid dihydrazide is preferred. One cross-linking agent can be used alone, or two or more can be used in combination.

[0200] The content of the crosslinking agent is preferably 1 to 50 parts by mass relative to 100 parts by mass of the polymer (C). If the content of the crosslinking agent is 1 part by mass or more, water resistance and heat resistance are more excellent. On the other hand, if the content of the crosslinking agent is 50 parts by mass or less, a good film is easily formed, and water resistance and heat resistance are more excellent.

[0201] The adherends of the adhesive include paper, wood, and plastic. Among them, wood is suitable. The adhesive disclosed in the present invention shows high adhesion even to coniferous trees with a high lipid content and broad-leaved trees with dense wood grains, and can therefore be used in applications such as laminated materials, plywood, decorative plywood, and fiberboard. In addition, the adhesive disclosed in the present invention can also be appropriately used as an adhesive for paper, in particular, an adhesive for paper straws.

[0202] [use]

[0203] The aqueous dispersion and aqueous emulsion disclosed in the present invention can be used for various purposes other than the above-mentioned purposes. Examples thereof are listed below, but the invention is not limited to these examples.

[0204] (1) Use of vinyl chloride dispersant: Dispersion stabilizer and dispersing aid for suspension polymerization of vinyl chloride and vinylidene chloride

[0205] (2) Application of coating agent: sizing agent, fiber processing agent, leather finishing agent, coating, antifogging agent, metal anticorrosive agent, galvanizing gloss agent, antistatic agent

[0206] (3) Adhesive / adhesive use: Adhesive, adhesive, rewetting adhesive, various adhesives, additives for cement or mortar

[0207] (4) Applications of dispersion stabilizers: dispersion stabilizers for organic / inorganic pigments in coatings and adhesives, dispersion stabilizers for emulsion polymerization of various vinyl compounds, post-emulsifiers for asphalt, etc.

[0208] (5) Paper processing applications: paper strength enhancers, oil / solvent resistance agents, smoothness enhancers, surface gloss improvers, gap fillers, barrier agents, light resistance enhancers, water resistance agents, dye / color developer dispersants, adhesion improvers, adhesives

[0209] (6) Agricultural use: pesticide adhesives, pesticide spreaders, agricultural coating agents, soil conditioners, erosion inhibitors, pesticide dispersants

[0210] (7) Medical / cosmetic applications: granulation binders, coating agents, emulsifiers, patches, binders, film preparation base materials, film forming agents

[0211] (8) Viscosity modifiers: thickeners, rheology modifiers

[0212] (9) Uses of coagulants: coagulants for suspended and dissolved matter in water, metal coagulants

[0213] (10) Film applications: water-soluble films, polarizing films, barrier films, fiber product packaging films, seed care sheets, vegetation sheets, seed tapes, hygroscopic films

[0214] (11) Application of formed products: fibers, films, sheets, pipes, tubes, leak-proof films, water-soluble fibers for chemical lace, sponges

[0215] (12) Application of resin raw materials: Raw materials for polyvinyl butyral, raw materials for photosensitive resins, raw materials for graft polymers, and raw materials for various gels

[0216] (13) Post-reaction uses: post-reaction uses with low molecular weight organic compounds, high molecular weight organic compounds and inorganic compounds.

[0217] The present disclosure includes various combinations of the above-described configurations within the scope of the technical concept of the present disclosure as long as the effects of the present disclosure can be exhibited. Example

[0218] The present disclosure will be described in further detail by way of examples. It should be noted that, hereinafter, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0219] Unless otherwise specified, "parts" and "%" refer to parts by mass and mass %, respectively.

[0220] [Content of ethylene units in ethylene-vinyl alcohol copolymer (A)]

[0221] The content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is determined by the content of the precursor or reacetylated product of the ethylene-vinyl alcohol copolymer (A), i.e., the ethylene-modified vinyl ester polymer. 1 H-NMR was obtained. Specifically, the ethylene-modified vinyl ester polymers of the samples of the examples and comparative examples were reprecipitated and purified three or more times using a mixed solution of n-hexane and acetone, and then dried under reduced pressure at 80°C for 3 days to prepare the ethylene-modified vinyl ester polymers for analysis. The ethylene-modified vinyl ester polymers for analysis were dissolved in DMSO-d6 and measured at 80°C using a nuclear magnetic resonance device. 1 H-NMR (500 MHz): The ethylene unit content was calculated by the following formula using the peak derived from the main chain methine protons of vinyl acetate (integrated value P: 4.7 to 5.2 ppm) and the peak derived from the main chain methylene protons of ethylene and vinyl acetate (integrated value Q: 1.0 to 1.6 ppm).

[0222] Ethylene unit content (mol%) = 100 × ((Q-2P) / 4) / P

[0223] [Viscosity average degree of polymerization of vinyl alcohol polymer]

[0224] The viscosity average degree of polymerization of the vinyl alcohol polymer (ethylene-vinyl alcohol copolymer (A) or PVA containing no ethylene unit) is measured in accordance with JIS K 6726: 1994. Specifically, when the degree of saponification of the vinyl alcohol polymer is less than 99.5 mol %, the vinyl alcohol polymer is saponified until the degree of saponification becomes 99.5 mol % or more, and the viscosity average degree of polymerization (P) is calculated using the following formula using the intrinsic viscosity [η] (liter / g) measured in water at 30°C. P=([η]×10 4 / 8.29) (1 / 0.62)

[0225] [Saponification degree of vinyl alcohol polymer]

[0226] The saponification degree of the vinyl alcohol polymer (ethylene-vinyl alcohol copolymer (A) or PVA containing no ethylene unit) can be determined by the method described in JIS K 6726:1994.

[0227] [Production Example 1]

[0228] A schematic diagram of the polymerization apparatus used is shown in Figure 1In a roughly cylindrical polymerization tank 1 [capacity: 7 kl, tank inner diameter D: 1.8 m] having a maximum mixing blade (manufactured by Sumitomo Heavy Industries, Ltd., stirring blade diameter (diameter) d: 1 m, blade (paddle) width b: 2 m] as a stirring blade 8, ethylene was introduced from a conduit 5 in such a manner that the ethylene pressure in the tank became 0.47 MPa, and a 1 mass % methanol solution of a polymerization initiator 2,2'-azobis-(4-methoxy-2,4-dimethylvaleronitrile) was introduced from a conduit 6 at a rate of 2.5 L / hr. In addition, a vinyl acetate-containing solution was introduced through an inlet pipe 10 and a heat exchanger 2. Liquid (vinyl acetate: 820 L / hr, methanol: 128 L / hr) is introduced into polymerization tank 1. In addition, ethylene-containing gas is introduced into heat exchanger 2 from polymerization tank 1 via conduit 3. The liquid containing vinyl acetate flows down along the surface of the tube, thereby absorbing ethylene, and is injected into polymerization tank 1 via conduit 4, mixed with the reaction liquid, and provided for continuous polymerization with ethylene. The polymerization liquid is continuously taken out from outlet pipe 9 so that the liquid level in polymerization tank 1 is constant. The polymerization rate of vinyl acetate at the outlet of polymerization tank 1 is adjusted to 28%. In addition, the stirring power Pv per unit volume is adjusted to 3 kW / m 3 , the Froude number Fr is 0.11. The reaction solution is stirred while the blade (paddle) is immersed in the reaction solution as a whole and the liquid surface is close to the upper end of the blade (paddle). The residence time of the reaction solution in the polymerization tank is 5 hours. The temperature at the outlet of the polymerization tank is 60°C. Methanol vapor is introduced into the continuously withdrawn polymerization solution to remove unreacted vinyl acetate monomers and obtain a methanol solution of ethylene-vinyl acetate copolymer (concentration 30% by mass).

[0229] A methanol solution of sodium hydroxide (concentration 4% by mass) as a saponification catalyst was added to the methanol solution of ethylene-vinyl acetate copolymer (concentration 30% by mass) obtained in the above polymerization step so that the molar ratio of sodium hydroxide to vinyl acetate unit in the above ethylene-vinyl acetate copolymer was 0.011. The ethylene-vinyl acetate copolymer solution and the saponification catalyst solution were mixed with a static mixer, and the obtained mixture was placed on a belt and kept at 40° C. for 18 minutes to allow saponification reaction to proceed. Then, the mixture was pulverized and dried to obtain an ethylene-vinyl alcohol copolymer (1). The obtained copolymer (1) had an ethylene unit content of 4.0 mol%, a viscosity average degree of polymerization of 1700, a saponification degree of 98.0 mol%, and a block characteristic of ethylene units of 0.92.

[0230] It should be noted that the stirring power per unit volume Pv (kW / m 3 ) is calculated by the following formula.

[0231] Pv=(Pt-Pe) / V

[0232] Here, Pt is the stirring power (kW) during the polymerization reaction, Pe is the stirring power (kW) when there is no load (when the polymerization tank is empty), and V is the amount of polymerization solution in the polymerization tank (m 3 ). In the above formula, Pe and Pt are calculated from the current value (A) and voltage value (V) of the mixer by the following formulas.

[0233] Pe(or Pt)=3 1 / 2 × voltage value × current value × power factor × efficiency / 1000

[0234] In addition, the Froude number Fr is calculated by the following formula.

[0235] Fr=n 2 ×d / g

[0236] (In the formula, n is the rotation speed of the stirring blade (rps), d is the diameter of the stirring blade (m), and g is the acceleration due to gravity (m / s 2 )).

[0237] [Block characteristics of ethylene units in ethylene-vinyl alcohol copolymer]

[0238] After saponification of the ethylene-vinyl alcohol copolymer to a saponification degree of 99.9 mol % or more, the copolymer was washed thoroughly with methanol and then dried under reduced pressure at 90° C. for 2 days. The resulting copolymer was dissolved in DMSO-d6 and chromatographed using a 500 MHz 13 C-NMR was measured at 80°C. From the obtained spectrum, the molar fraction of the vinyl alcohol / ethylene 2-unit chain (AE), the molar fraction of the vinyl alcohol unit (A), and the molar fraction of the ethylene unit (E) were used to assign and calculate the block characteristics (η) of the ethylene unit by the following formula: η = (AE) / {2 × (A) × (E)}

[0239] [Production Examples 2 to 4]

[0240] Ethylene-vinyl alcohol copolymers (2) to (4) were produced in the same manner as in Production Example 1, except that the feed amounts of ethylene, vinyl acetate, methanol and initiator, polymerization rate, stirring power Pv, Froude number Fr during polymerization, and the concentration of the ethylene-vinyl ester copolymer solution and the molar ratio of sodium hydroxide during saponification were changed as shown in Table 1.

[0241] [Production Example 5]

[0242] Ethylene-vinyl alcohol copolymer (5) was produced in the same manner as in Production Example 1 except that the feed amounts of ethylene, vinyl acetate, methanol and initiator during polymerization, the polymerization rate, the stirring power per unit volume Pv, the Froude number Fr, the method of supplying vinyl acetate, the concentration of the ethylene-vinyl ester copolymer solution during saponification and the molar ratio of sodium hydroxide were changed as shown in Table 1, and a two-stage inclined impeller [agitating impeller diameter (diameter) d: 1.5 m, impeller (blade) width b: 0.88 m] was used as the stirring impeller 8. It should be noted that the two-stage inclined impeller does not belong to a wide impeller because the impeller (blade) width b is small.

[0243] [Production Example 6]

[0244] Ethylene-vinyl alcohol copolymer (6) was produced by the same method as in Production Example 1 except that the feed amounts of ethylene, vinyl acetate, methanol and initiator and the polymerization rate during polymerization, the stirring power per unit volume Pv, the Froude number Fr, the concentration of the ethylene-vinyl ester copolymer solution and the molar ratio of sodium hydroxide during saponification were changed as shown in Table 1, and an anchor wing [stirring wing diameter (diameter) d: 1.7 m, wing (paddle) width b: 0.85 m] was used as the stirring wing 8. It should be noted that the anchor wing does not belong to a wide paddle wing because the wing (paddle) width b is small.

[0245] [Table 1]

[0246] .

[0247] [Example I-1]

[0248] 100 parts by mass of ethylene-vinyl alcohol copolymer (1) was dissolved in 2150 parts by mass of water to prepare a 4% aqueous solution of ethylene-vinyl alcohol copolymer (1). 250 parts by mass of a 2% aqueous dispersion of unmodified CNF (aspect ratio of about 200, average fiber diameter of 50 nm, average fiber length of 10 μm) was added to the aqueous solution, and stirred for 1 hour with a magnetic stirrer to obtain an aqueous dispersion. The content of CNF in the aqueous dispersion was 5 parts by mass relative to 100 parts by mass of ethylene-vinyl alcohol copolymer (1).

[0249] [Determination of membrane swelling degree and dissolution rate]

[0250] The aqueous dispersion obtained in Example I-1 was cast on a PET film at 20°C and 65% RH and dried at room temperature for 7 days to obtain a coating formed with a dry film. The dry film was peeled off from the coating to obtain a film with a thickness of 50 μm. The film was immersed in water at 20°C for 20 hours, and the swelling degree and dissolution rate of the film were determined using the following formula. The smaller these values ​​are, the better the water resistance of the film. The results are shown in Table 2.

[0251] Swelling degree (times) = (mass of sample after water immersion) / (mass of sample after water immersion and drying)

[0252] Dissolution rate (mass %) = [{(dry mass of sample before water immersion) - (dry mass of sample after water immersion)} / (dry mass of sample before water immersion)] × 100

[0253] [Measurement of film strength and elongation]

[0254] By the same method as the determination of the swelling degree and dissolution rate of the film, a film with a thickness of 50 μm was obtained. The film was cut into a width of 10 mm, and after humidity adjustment at 20°C and 65% RH for 1 week, the strength and elongation were measured using a precision universal testing machine "Autograph AG-IS" manufactured by Shimadzu Corporation under the conditions of a chuck spacing of 50 mm and a tensile speed of 100 mm / min, and the tensile elastic modulus, breaking point strain and breaking point stress were obtained. It should be noted that the measurement was to measure each sample 5 times and find the average value. The results are shown in Table 3.

[0255] [Examples I-2 to I-5]

[0256] The aqueous dispersion was obtained in the same manner as in Example I-1 except that the type of ethylene-vinyl alcohol copolymer (A) and the content of CNF were changed as shown in Table 2. The aqueous dispersion was used to prepare a film by the aforementioned method, and the swelling degree, dissolution rate, strength, and elongation of the film were evaluated. The results are shown in Tables 2 and 3.

[0257] [Comparative Example I-1]

[0258] A 4 mass % aqueous solution of ethylene-vinyl alcohol copolymer (1) was prepared in the same manner as in Example I-1. 250 mass parts of water was added to the aqueous solution, and the mixture was stirred in the same manner as in Example I-1 to obtain an aqueous solution. The aqueous solution was used to prepare a film in the aforementioned manner, and the swelling degree, dissolution rate, strength, and elongation of the film were evaluated. The results are shown in Tables 2 and 3.

[0259] [Comparative Example I-2]

[0260] The aqueous solution was obtained in the same manner as in Comparative Example I-1 except that the type of ethylene-vinyl alcohol copolymer (A) was changed as shown in Table 2. The aqueous solution was used to prepare a film by the aforementioned method, and the swelling degree, dissolution rate, strength, and elongation of the film were evaluated. The results are shown in Tables 2 and 3.

[0261] [Comparative Examples I-3 to I-6]

[0262] A water dispersion was obtained in the same manner as in Example I-1 except that the PVA containing no ethylene units described in Table 2 was used instead of the ethylene-vinyl alcohol copolymer (A) and the content of CNF was changed as shown in Table 2. The water dispersion was used to prepare a film by the aforementioned method, and the swelling degree, dissolution rate, strength and elongation of the film were evaluated. The results are shown in Tables 2 and 3.

[0263] [Comparative Examples I-7, I-8]

[0264] An aqueous solution was obtained in the same manner as in Comparative Example I-1 or Comparative Example I-2 except that the PVA containing no ethylene unit described in Table 3 was used instead of the ethylene-vinyl alcohol copolymer (A). A film was prepared using the aqueous solution by the aforementioned method, and the strength and elongation of the film were evaluated. The results are shown in Table 3.

[0265] [Comparative Example I-9]

[0266] An attempt was made to prepare an aqueous dispersion using the ethylene-vinyl alcohol copolymer (6) described in Table 2 instead of the ethylene-vinyl alcohol copolymer (1) of Example I-1. However, the ethylene-vinyl alcohol copolymer (6) was insoluble in water, and thus the aqueous dispersion could not be prepared or evaluated.

[0267] [Table 2]

[0268]

[0269] [Table 3]

[0270]

[0271] The films made from the aqueous dispersions of Comparative Example I-3 (5 parts by mass of CNF) and Comparative Example I-4 (30 parts by mass of CNF) showed improved tensile modulus and stress at break, but significantly reduced strain at break compared to the films made from the aqueous solution of Comparative Example I-7 (0 parts by mass of CNF). On the other hand, the films made from the aqueous dispersions of Example I-1 (5 parts by mass of CNF) and Example I-2 (30 parts by mass of CNF) showed improved tensile modulus and stress at break, and suppressed reduction in strain at break compared to the films made from the aqueous solution of Comparative Example I-1 (0 parts by mass of CNF).

[0272] In the case of changing the type of vinyl alcohol polymer contained in the aqueous dispersion, it can also be said that there is the same tendency. The film made by the aqueous dispersion of Comparative Example I-5 (5 parts by mass of CNF) and Comparative Example I-6 (30 parts by mass of CNF) is compared to the film made by the aqueous solution of Comparative Example I-8 (0 parts by mass of CNF), and the tensile elastic modulus and the stress at the breaking point are improved, but the strain at the breaking point is significantly reduced. On the other hand, the film made by the aqueous dispersion of Example I-3 (5 parts by mass of CNF) and Example I-4 (30 parts by mass of CNF) is compared to the film made by the aqueous solution of Comparative Example I-2 (0 parts by mass of CNF), and the tensile elastic modulus and the stress at the breaking point are greatly improved, and the reduction of the strain at the breaking point is suppressed.

[0273] [Example II-1]

[0274] 100 parts by mass of ethylene-vinyl alcohol copolymer (1) was dissolved in 900 parts by mass of water to prepare a 10% aqueous solution of ethylene-vinyl alcohol copolymer (1). 250 parts by mass of a 2% aqueous dispersion of unmodified CNF (aspect ratio of about 200, average fiber diameter of 50 nm, average fiber length of 10 μm) was added to the aqueous solution, and then 500 parts by mass of water was added, and stirred for 1 hour with a magnetic stirrer to obtain a coating agent. The content of CNF in the coating agent was 5 parts by mass relative to 100 parts by mass of ethylene-vinyl alcohol copolymer (1), and the content of ethylene-vinyl alcohol copolymer (1) and CNF in the coating agent was 6% by mass in total. The evaluation of the coating agent, the preparation and evaluation of the coated paper were carried out by the method described later. The results are shown in Table 4.

[0275] [Production of coated paper for release paper using a coating agent]

[0276] The coating agent obtained in Example II-1 was applied to a glass paper having a basis weight of 64 gsm by hand using a wire rod (rod coater). The coated paper was then dried at 105°C for 1 minute using a drum-type rotary drying dryer to produce coated paper. The coating amount of the coating agent converted to solid content was 1.0 gsm (single side). The coated paper obtained was humidified at 20°C and 65% RH for 72 hours, and the physical properties of the coated paper were measured.

[0277] [Production of coated paper for oil-resistant paper using a coating agent]

[0278] The coating agent obtained in Example II-1 was applied by hand using a wire rod to PPC (plain paper copier) paper (premium paper) with a basis weight of 70 gsm. Then, the coated paper was dried at 105°C for 1 minute using a drum-type rotary drying machine. The coating amount of the coating agent converted by solid content was 3.0 gsm (single side). After the coated paper was humidified at 20°C and 65% RH for 72 hours, the physical properties of the coated paper were measured.

[0279] [Roller contamination test of coated paper]

[0280] The coated paper prepared by the above steps was humidified at 40°C and 90% RH for 24 hours. The moisture content of the coated paper at this time was about 10%. While maintaining this moisture content as much as possible, the coated paper was transferred once in a drum type rotary dryer, and the transfer of the coated surface to the drum roller surface was observed and evaluated in the following three stages.

[0281] ○: Transfer to the applied surface was hardly observed.

[0282] △: Part of the applied surface was transferred.

[0283] ×: A large amount of the coated surface was transferred.

[0284] [Water resistance test of coated paper]

[0285] About 0.1 g of ion-exchanged water at 20° C. was dropped onto the surface of the coated paper, and then the surface was wiped with a fingertip, and the dissolution state of the coating agent was observed and evaluated in the following five levels.

[0286] 5-Excellent water resistance, no sticky feeling.

[0287] 4-Although it has a slimy feeling, there is no change in the coating layer.

[0288] 3- A portion of the coating agent is emulsified.

[0289] 2-Overall emulsification of the coating agent.

[0290] 1-The coating agent dissolves.

[0291] [Evaluation for release paper applications: air permeability measurement]

[0292] The air permeability of the coated paper is measured using a Wangyan type slippery air permeability tester in accordance with JIS P 8117: 2009. The air permeability is preferably 35,000 sec or more.

[0293] [Evaluation for release paper applications: Toluene barrier test]

[0294] After colored toluene (red) (5×5 cm) was applied to the coated surface of the coated paper, the degree of penetration to the back side (uncoated surface) (small red spots to coloring of the entire coated surface) was observed and evaluated according to the following criteria.

[0295] 5-No spots on the back

[0296] 4-Produce spots (1, 2)

[0297] 3- Generates a large number of spots (about 10-20% of the toluene-coated surface)

[0298] 2- Approximately 20-70% of the coated surface is colored

[0299] 1- The entire coating surface (about 70% or more) is colored

[0300] [Evaluation for oil-resistant paper applications: KIT test, folding KIT test]

[0301] According to TAPPI No. T559cm-02, the KIT test of the flat surface and the bent portion of the coated surface was performed. The evaluation was performed visually. It should be noted that the KIT value of commercially available oil-resistant paper using fluororesin is usually above grade 5, and the oil resistance without problems in general use is above grade 5. Therefore, the oil resistance of the coated paper is preferably above grade 5, and in applications requiring higher oil resistance, it is more preferably above grade 7, and further preferably above grade 10.

[0302] In the KIT test of the folded portion, the coated paper was folded into two parts so that the coated surface was the outer surface, and a pressure of 1.0 mm, 0.7 mm and 2.5 kgf / cm2 was applied from the folded portion. 2 ・Seconds, the coated paper is pressed to completely form a fold line, and then the coated paper is unfolded and the oil resistance of the fold line portion is measured according to TAPPI No. T559cm-02. The measurement is performed visually. Regarding the folded portion, the oil resistance without any problem is also 5 or higher, so the oil resistance of this portion is preferably 5 or higher, more preferably 7 or higher in applications requiring higher oil resistance, and further preferably 10 or higher.

[0303] [Examples II-2 to II-7]

[0304] The coating agent was obtained in the same manner as in Example II-1 except that the type of ethylene-vinyl alcohol copolymer (A) and the content of CNF were changed as shown in Table 4. The coating agent was evaluated by the aforementioned method. Coated paper was prepared using the coating agent by the aforementioned method and evaluated. The results are shown in Table 4.

[0305] [Comparative Examples II-1 to II-3]

[0306] A coating agent was obtained in the same manner as in Example II-1 except that the PVA containing no ethylene units shown in Table 1 was used instead of the ethylene-vinyl alcohol copolymer (1) and the CNF content was set as shown in Table 4. The coating agent was evaluated by the aforementioned method. Coated paper was prepared and evaluated using the coating agent and the aforementioned method. The results are shown in Table 4.

[0307] [Comparative Example II-4]

[0308] A 10% aqueous solution of PVA (1) was prepared in the same manner as in Example II-1, except that PVA (1) not containing ethylene units shown in Table 4 was used instead of ethylene-vinyl alcohol copolymer (1). 750 parts by weight of water was added to the aqueous solution, and the mixture was stirred for 1 hour with a magnetic stirrer to obtain a coating agent. The coating agent was evaluated by the aforementioned method. Coated paper was prepared and evaluated using the coating agent and the aforementioned method. The results are shown in Table 4.

[0309] [Comparative Example II-5]

[0310] A 10% aqueous solution of ethylene-vinyl alcohol copolymer (1) was prepared in the same manner as in Example II-1. 750 parts by mass of water was added to the aqueous solution and stirred for 1 hour with a magnetic stirrer to obtain a coating agent. The coating agent was evaluated by the aforementioned method. Coated paper was prepared and evaluated using the coating agent and the aforementioned method. The results are shown in Table 4.

[0311] [Comparative Example II-6]

[0312] An attempt was made to prepare a coating agent using ethylene-vinyl alcohol copolymer (6) shown in Table 4 instead of ethylene-vinyl alcohol copolymer (1), but the ethylene-vinyl alcohol copolymer (6) was not soluble in water and could not be prepared. Therefore, evaluation of the coating agent and preparation and evaluation of coated paper could not be performed.

[0313] [Table 4]

[0314]

[0315] The coated paper (Example II-1) made using a coating agent composed of an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and CNFs showed good results in the roller contamination test compared to the case without CNFs (Comparative Example II-5), and the release paper also had excellent air permeability, water resistance, solvent barrier properties, and oil resistance when folded. The coating agent (Example II-1) composed of an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and CNFs showed excellent air permeability, water resistance, solvent barrier properties, and oil resistance when folded compared to the coating agent (Comparative Example II-1) composed of an aqueous dispersion containing PVA and CNFs that does not contain ethylene units.

[0316] [Example III-1]

[0317] 100 parts by mass of ethylene-vinyl alcohol copolymer (1) was dissolved in 1150 parts by mass of water to prepare an 8% by mass aqueous solution of ethylene-vinyl alcohol copolymer (1). 250 parts by mass of a 2% by mass aqueous dispersion of unmodified CNF (aspect ratio of about 200, average fiber diameter of 50 nm, average fiber length of 10 μm) was added to the aqueous solution, and stirred for 1 hour with a magnetic stirrer to obtain an aqueous dispersion. The content of CNF in the aqueous dispersion was 5 parts by mass relative to 100 parts by mass of ethylene-vinyl alcohol copolymer (1).

[0318] (Manufacturing of Multilayer Structure)

[0319] The anchor coating agent (adhesive) was applied to a stretched polyethylene terephthalate (OPET) film (substrate) having a thickness of 15 μm as layer (2) to form an adhesive layer on the surface of the OPET film. The aqueous dispersion obtained above was applied to the surface of the adhesive layer at 40°C using a gravure coater, and then dried at 120°C to form a layer (1). In order to promote the reaction of the anchor coating agent, the film was further heat-treated at 160°C for 120 seconds to obtain a multilayer structure. The thickness of the layer (1) was 2 μm.

[0320] [Oxygen barrier properties]

[0321] The multilayer structure obtained in Example III-1 was humidified for 5 days at 20°C and 85% RH, and then the oxygen permeation rate X (cc / m 2 The results are shown in Table 5.

[0322] Temperature: 20℃

[0323] Humidity on oxygen supply side: 85%RH

[0324] Humidity of carrier gas side: 85%RH

[0325] Carrier gas flow rate: 10mL / min

[0326] Oxygen pressure: 1.0atm

[0327] Carrier gas pressure: 1.0atm.

[0328] [Oxygen barrier properties after bending load]

[0329] The multilayer structure obtained in Example III-1 was subjected to bending load three times using Gelbo Flex, and the oxygen permeation rate Y (cc / m 2The results are shown in Table 5.

[0330] [Examples III-2 to III-5]

[0331] A multilayer structure was obtained in the same manner as in Example III-1 except that the type of ethylene-vinyl alcohol copolymer (A) and the content of CNF were changed as shown in Table 5. Table 5 shows the oxygen permeation rate X and the oxygen permeation rate Y after bending load of the obtained multilayer structure.

[0332] [Comparative Example III-1]

[0333] An 8 mass % aqueous solution of ethylene-vinyl alcohol copolymer (1) was prepared in the same manner as in Example III-1. 250 parts by mass of water was added to the aqueous solution, and the mixture was stirred in the same manner as in Example III-1 to obtain an aqueous solution. A multilayer structure was prepared in the same manner as in Example III-1 except that the aqueous solution was used. The oxygen permeation rate X and the oxygen permeation rate Y after bending load of the multilayer structure are shown in Table 5.

[0334] [Comparative Example III-2]

[0335] An aqueous solution was obtained in the same manner as in Comparative Example III-1 except that the type of ethylene-vinyl alcohol copolymer (A) was changed as shown in Table 5. A multilayer structure was prepared using the aqueous solution in the same manner as described above. The oxygen permeation rate X and the oxygen permeation rate Y after bending load of the multilayer structure are shown in Table 5.

[0336] [Comparative Examples III-3 to III-6]

[0337] The aqueous dispersion was obtained in the same manner as in Example III-1 except that the PVA containing no ethylene unit described in Table 5 was used instead of the ethylene-vinyl alcohol copolymer (A) and the content of CNF was changed as shown in Table 5. A multilayer structure was prepared in the same manner as in Example III-1 except that the aqueous dispersion was used. The oxygen permeation rate X and the oxygen permeation rate Y after bending load of the multilayer structure are shown in Table 5.

[0338] [Comparative Examples III-7, III-8]

[0339] An aqueous solution was obtained in the same manner as in Comparative Example III-1 except that the PVA containing no ethylene units described in Table 5 was used instead of the ethylene-vinyl alcohol copolymer (A). A multilayer structure was prepared using the aqueous solution in the aforementioned manner. The oxygen permeation rate X and the oxygen permeation rate Y after bending load of the multilayer structure are shown in Table 5.

[0340] [Comparative Example III-9]

[0341] An attempt was made to use ethylene-vinyl alcohol copolymer (6) as shown in Table 5 instead of ethylene-vinyl alcohol copolymer (1) to produce a multilayer structure. However, ethylene-vinyl alcohol copolymer (6) is insoluble in water, and thus the preparation of a coating agent, the production of a multilayer structure, and the evaluation thereof could not be performed.

[0342] [Table 5]

[0343]

[0344] The coating agent composed of an aqueous dispersion containing ethylene-vinyl alcohol copolymer (A) and CNF (Example III-1) has excellent oxygen barrier properties, especially oxygen barrier properties after bending load, compared with the case without CNF (Comparative Example III-1). The same results were obtained when the viscosity-average degree of polymerization and the content of ethylene units of the ethylene-vinyl alcohol copolymer (A) were changed (comparison between Example III-3 and Comparative Example III-2). The coating agent composed of an aqueous dispersion containing ethylene-vinyl alcohol copolymer (A) and CNF (Example III-1) has excellent oxygen barrier properties compared with the coating agent composed of an aqueous dispersion containing PVA and CNF without ethylene units (Comparative Example III-3).

[0345] [Example IV-1]

[0346] 285 g of ion exchange water was placed in a 1-liter glass polymerization tank equipped with a reflux condenser, a dropping funnel, a thermometer, and a nitrogen blowing port, and heated to 85°C. 21.0 g of ethylene-vinyl alcohol copolymer (A) (viscosity average polymerization degree 1700, saponification degree 98 mol%, ethylene unit content 4 mol%) was added and stirred for 45 minutes to dissolve. 0.3 g of sodium acetate was further added, mixed and dissolved. Next, the aqueous solution in which the copolymer was dissolved was cooled, replaced with nitrogen, and heated to 60°C while stirring at 200 rpm. After 2.4 g of a 20% aqueous solution of tartaric acid and 3.2 g of 5% hydrogen peroxide were injected, 28 g of vinyl acetate was added, and polymerization was initiated. 30 minutes after the initiation of polymerization, the initial polymerization was confirmed to be completed (the residual amount of vinyl acetate was less than 1%). After injecting 1 g of a 10% aqueous solution of tartaric acid and 3.2 g of a 5% hydrogen peroxide solution, 252 g of vinyl acetate was continuously added over 2 hours, and the polymerization temperature was maintained at 80° C. to terminate the polymerization. 7.4 parts by mass of a 5% aqueous dispersion of unmodified cellulose nanofibers (aspect ratio of about 200, average fiber diameter of 50 nm, average fiber length of 10 μm) was added to 100 parts by mass of the aqueous emulsion, and the mixture was slowly mixed and stirred using an anchor-type stirring blade to obtain an aqueous emulsion (Em-1).

[0347] [Heat-resistant adhesiveness]

[0348] The heat-resistant adhesiveness was evaluated according to WATT'91 (DIN EN 14257:2019). The results are shown in Table 1.

[0349] (Bonding conditions)

[0350] Bonded material:Buna rubber / Buna rubber

[0351] Coating amount: 200g / m 2

[0352] Pressing conditions: 20℃, 2 hours, pressure 0.7N / mm 2

[0353] Curing conditions: 20℃, 1 week.

[0354] (Measurement conditions)

[0355] After standing in a dryer at 80°C for 1 hour, the test piece was taken out and the adhesive strength (unit: N / mm 2 ).

[0356] [Water resistance of film]

[0357] The aqueous emulsion obtained in Example IV-1 was cast on a PET film at 20°C and 65% RH and dried at room temperature for 7 days to obtain a coating formed with a dry film. The dry film was peeled off from the coating to obtain a film with a thickness of 400 μm. The film was immersed in water at 20°C for 20 hours, and the water absorption and dissolution rate of the film were determined using the following formula. The smaller these values, the better the water resistance of the film. The results are shown in Table 6.

[0358] Water absorption (mass %) = {(mass of sample after water immersion) / (mass of sample after water immersion and drying) × 100}-100

[0359] Dissolution rate (mass %)=[{(dry mass of sample before water immersion)−(dry mass of sample after water immersion)} / (dry mass of sample before water immersion)]×100.

[0360] [Examples IV-2 to IV-5]

[0361] As shown in Table 6, the type and addition amount of ethylene-vinyl alcohol copolymer (A) and the addition amount of CNF were changed. Polymerization and addition of CNF were performed in the same manner as in Example IV-1 to obtain aqueous emulsions (Em-2 to Em-5). The heat-resistant adhesiveness and water resistance of the aqueous emulsions (Em-2 to Em-5) were evaluated by the aforementioned method. The results are shown in Table 6.

[0362] [Comparative Example IV-1]

[0363] The type and addition amount of ethylene-vinyl alcohol copolymer (A) were changed as shown in Table 6, and polymerization was carried out in the same manner as in Example IV-1 to obtain an aqueous emulsion. Without adding CNF, the aqueous emulsion was directly used as an aqueous emulsion (Em-A). The heat-resistant adhesiveness and water resistance of the aqueous emulsion (Em-A) were evaluated by the aforementioned method. The results are shown in Table 6.

[0364] [Comparative Example IV-2]

[0365] Polymerization and addition of CNF were performed in the same manner as in Example IV-1, except that polyvinyl alcohol containing no ethylene units as shown in Table 6 was used instead of ethylene-vinyl alcohol copolymer (A), to obtain aqueous emulsion (Em-B). The heat-resistant adhesiveness and water resistance of the film of aqueous emulsion (Em-B) were evaluated by the aforementioned method. The results are shown in Table 6.

[0366] [Comparative Example IV-3]

[0367] The type and amount of ethylene-vinyl alcohol copolymer (A) and the amount of CNF added were changed as shown in Table 6. Polymerization and addition of CNF were performed in the same manner as in Example IV-1 to obtain an aqueous emulsion (Em-C). The heat-resistant adhesiveness and water resistance of the aqueous emulsion (Em-C) were evaluated by the aforementioned method. The results are shown in Table 6.

[0368] [Table 6]

[0369]

[0370] For the aqueous emulsion not containing CNF (Comparative Example IV-1), compared with the aqueous emulsion whose CNF content is within the range specified in the present disclosure (Example IV-4), the heat-resistant adhesiveness and the water resistance of the film are low. On the other hand, for the aqueous emulsion whose CNF content is more than the range specified in the present disclosure (Comparative Example IV-3), the film collapsed and the water resistance of the film could not be measured, and the heat-resistant adhesiveness was low. For the aqueous emulsion using polyvinyl alcohol not containing ethylene units (Comparative Example IV-2), compared with the aqueous emulsion using ethylene-vinyl alcohol copolymer (A) (Example IV-1), the heat-resistant adhesiveness and the water resistance of the film are poor. On the other hand, as shown in Examples IV-1 to IV-5, the aqueous emulsion of the present disclosure has excellent heat-resistant adhesiveness and the water resistance of the film.

Claims

1. A water dispersion comprising an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers, wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%, The viscosity average polymerization degree of the ethylene-vinyl alcohol copolymer (A) is 200 to 5000, The saponification degree of the ethylene-vinyl alcohol copolymer (A) is 80 to 99.9 mol%. The block characteristic of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) is 0.70 or more and 1.1 or less.

2. The aqueous dispersion according to claim 1, wherein the viscosity average degree of polymerization of the ethylene-vinyl alcohol copolymer (A) is 250 to 4500.

3. The aqueous dispersion according to claim 1 or 2, wherein the saponification degree of the ethylene-vinyl alcohol copolymer (A) is 83 to 99.5 mol%. 4 . The aqueous dispersion according to claim 1 , wherein the content of the cellulose nanofibers is 0.1 to 40 parts by mass based on 100 parts by mass of the ethylene-vinyl alcohol copolymer (A). 5 . The aqueous dispersion according to claim 1 , wherein the total content of the ethylene-vinyl alcohol copolymer (A) and the cellulose nanofibers in the aqueous dispersion is 0.1 to 30% by mass.

6. The aqueous dispersion according to claim 1 or 2, wherein the block characteristic of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) is 0.90 to 0.

99.

7. An aqueous emulsion comprising an ethylene-vinyl alcohol copolymer (A) as a dispersant, a polymer (C) containing ethylenically unsaturated monomer units as a dispersoid, and cellulose nanofibers, wherein the content of the cellulose nanofibers is 0.1 to 40 parts by mass relative to 100 parts by mass of the ethylene-vinyl alcohol copolymer (A), The total content of the ethylene-vinyl alcohol copolymer (A) and the cellulose nanofibers is 2 to 35 parts by mass based on 100 parts by mass of the polymer (C). The content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1 mol% or more and less than 20 mol%, The viscosity average polymerization degree of the ethylene-vinyl alcohol copolymer (A) is 200 to 5000, The saponification degree of the ethylene-vinyl alcohol copolymer (A) is 80 to 99.9 mol%. The block characteristic of the ethylene unit of the ethylene-vinyl alcohol copolymer (A) is 0.70 or more and 1.1 or less. 8 . The aqueous emulsion according to claim 7 , wherein the total content of the ethylene-vinyl alcohol copolymer (A) and the cellulose nanofibers is 2.5 to 30 parts by mass based on 100 parts by mass of the polymer (C). 9 . The aqueous emulsion according to claim 7 , wherein the content of ethylene units in the ethylene-vinyl alcohol copolymer (A) is 1.5 mol % or more and less than 15 mol %. 10 . The aqueous emulsion according to claim 7 , wherein the total content of the ethylene-vinyl alcohol copolymer (A), the polymer (C) and the cellulose nanofibers in the solid content of the aqueous emulsion is 55% by mass or more.

11. The aqueous emulsion according to claim 7 or 8, wherein the polymer (C) contains 70% by mass or more of monomer units derived from at least one selected from vinyl ester monomers, (meth)acrylate monomers, styrene monomers and diene monomers, based on all monomer units. 12 . A coating agent comprising the aqueous dispersion according to claim 1 or the aqueous emulsion according to claim 7 . The coating agent according to claim 12 , which is a paper coating agent.

14. Coated paper comprising paper on which the coating agent according to claim 13 is coated.

15. The coated paper according to claim 14, which is a release paper base paper or an oil-resistant paper.

16. A multilayer structure comprising a substrate comprising a resin, wherein the coating agent according to claim 12 is applied onto the substrate. 17 . The multilayer structure according to claim 16 , wherein the resin is at least one resin selected from the group consisting of polyolefin resins, polyester resins and polyamide resins.

18. A packaging material comprising the multilayer structure according to claim 16 or 17.

19. An adhesive comprising the aqueous dispersion according to any one of claims 1 to 6 or the aqueous emulsion according to any one of claims 7 to 11.

20. A method for producing an aqueous emulsion according to any one of claims 7 to 11, comprising: a step (1) of obtaining an aqueous emulsion by emulsion polymerization of ethylenically unsaturated monomers in the presence of an ethylene-vinyl alcohol copolymer (A); and a step (2) of blending cellulose nanofibers into the aqueous emulsion.

21. A method for producing an aqueous emulsion according to any one of claims 7 to 11, comprising: a step (3) of obtaining an aqueous dispersion containing an ethylene-vinyl alcohol copolymer (A) and cellulose nanofibers; and a step (4) of mixing the aqueous dispersion with an ethylenically unsaturated monomer to carry out emulsion polymerization.

Citation Information

Patent Citations

  • adhesive

    JP1998121017A

  • Paper tube adhesive and paper tube using the same

    JP1999106727A

  • Cellulose nanofiber compound polyvinyl alcohol-based polymer composition

    JP2010242063A

  • Method for producing composition containing cellulose nanofiber and polyvinyl alcohol-based polymer

    JP2019156915A

  • Resin composition for forming a gas barrier layer

    JP6226096B1